Quality management method in molding step of outer packaging material for electricity storage device, method for manufacturing electricity storage device, outer packaging material for electricity storage device, and electricity storage device
By measuring the reflected light L* value of the outer packaging material for electrical storage devices under the measurement conditions of SCI mode, field of view 10° and light source F2, the problem of whitening of bending parts and difficult to detect fine cracks during the forming process is solved, and high-precision quality management and improvement of appearance quality are achieved.
Patent Information
- Application Number
- CN202411677428.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-08-19
- Publication Date
- 2025-03-04
AI Technical Summary
The existing outer packaging materials for electric storage devices are prone to whitening problems in the bent parts during the forming process, resulting in poor appearance and difficult to confirm fine cracks through visual inspection.
Under the measurement conditions of SCI mode, field of view 10° and light source F2, the L* value in the L*b* color space of reflected light is measured, and the quality of the outer packaging material for power storage devices is judged by the absolute value of the difference of L* values.
It realizes high-precision quality management of outer packaging materials for electrical storage devices, can effectively identify and eliminate whitening and fine cracks, and ensure the appearance quality of the product.
Smart Images

Figure BDA0005147379120000271 
Figure BDA0005147379120000281 
Figure BDA0005147379120000461
Abstract
Description
[0001] This case is a divisional application of a patent application with an application date of August 19, 2020, application number 202080058608.3 (international application number PCT / JP2020 / 031241), and an invention name of "Quality management method in the molding process of outer packaging material for storage device, manufacturing method of storage device, outer packaging material for storage device and storage device". Technical Field
[0002] The present invention relates to a quality control method in a molding process of an outer packaging material for an electric storage device, a method for manufacturing an electric storage device, an outer packaging material for an electric storage device, and an electric storage device. Background Art
[0003] In the prior art, various types of power storage devices have been developed, and in all power storage devices, outer packaging materials have become indispensable components in order to seal power storage device components such as electrodes and electrolytes. In the prior art, as outer packaging materials for power storage devices, metal outer packaging materials are mostly used.
[0004] On the other hand, in recent years, with the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., various shapes of power storage devices are required, and thinning and lightening are also required. However, the metal outer packaging materials for power storage devices commonly used in the prior art have the disadvantages of being difficult to follow the diversification of shapes and having a limit to lightening.
[0005] Therefore, in recent years, as an outer packaging material for power storage devices that can be easily processed into various shapes and can be thinned and lightened, a film-like laminated body in which a base layer / barrier layer / thermofusible resin layer are laminated in this order has been proposed (see, for example, Patent Document 1).
[0006] In such an outer packaging material for a storage device, a recess is usually formed by cold forming, and storage device elements such as electrodes and electrolyte are arranged in the space formed by the recess, and a heat-fusible resin layer is heat-fused to obtain a storage device in which the storage device elements are accommodated inside the outer packaging material for the storage device.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-287971 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In the outer packaging material for storage devices formed by the above-mentioned film-like laminate, the outer packaging material for storage devices has a curved portion due to the formation of a recessed portion for accommodating the storage device element. In this curved portion, the outer packaging material for storage devices is stretched, so sometimes the surface portion may be whitened. The whitening of the outer packaging material for storage devices due to forming may lead to poor appearance of the storage device, so it becomes the subject of quality management during the forming of the outer packaging material for storage devices. In this quality management, for example, in the case where the outer packaging material for storage devices is colored or the degree of whitening is severe, the presence or absence of whitening can be confirmed by visual inspection.
[0012] However, the inventors of the present invention have found that although it is difficult to visually confirm whitening in the curved portion forming the concave portion of the outer packaging material for a storage device, very fine cracks are sometimes formed when the curved portion (the curved portion of the outer surface of the outer packaging material for a storage device) is observed using a scanning electron microscope, etc. Therefore, it is clear that a new quality management method in the molding process of the outer packaging material for a storage device is needed.
[0013] Under such circumstances, a main object of the present invention is to provide a new quality control method in a molding process of an outer packaging material for an electric storage device.
[0014] Methods for solving problems
[0015] In order to solve the above technical problems, the inventors of the present invention conducted in-depth research. As a result, it was found that: the outer packaging material for storage devices to be inspected was extracted from the outer packaging material for storage devices in which a concave portion was formed in the molding process of the outer packaging material for storage devices, and the L of the reflected light was measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for storage devices to be inspected where the concave portion was formed, respectively, under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b * L in color space * Value, based on L * The size of the difference between the values (i.e. L * The absolute value of the difference between the values is used to determine whether the outer packaging material for a storage device having a recessed portion is a qualified product. This is compared with the conventional determination by visual inspection, and quality management can be performed with high accuracy.
[0016] The present invention has been completed through further research based on these findings. That is, the present invention provides the following aspects.
[0017] A quality management method in a forming process of an outer packaging material for a storage device,
[0018] The quality management method takes an outer packaging material for an electric storage device as an object of quality management, the outer packaging material for an electric storage device being composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside, the outer packaging material for an electric storage device being formed in a manner protruding from the heat-fusible resin layer side to the base layer side, and having a recessed portion capable of accommodating an electric storage device element formed on the heat-fusible resin layer side,
[0019] The quality control method includes a determination step in which an outer packaging material for a storage device to be inspected is extracted from an outer packaging material for a storage device having a recessed portion, and the L of reflected light is measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for the storage device to be inspected, respectively, under the measurement conditions of an SCI method, a field of view of 10°, and a light source of F2. * a * b * L in color space * Value, based on L * The magnitude of the difference between the two values is used to determine whether the outer packaging material for a power storage device having the recessed portion is a qualified product.
[0020] Effects of the Invention
[0021] According to the present invention, a new quality control method in the molding process of an outer packaging material for a storage device can be provided. Furthermore, according to the present invention, a method for manufacturing an outer packaging material for a storage device using the quality control method can be provided. Furthermore, according to the present invention, an outer packaging material for a storage device that is judged to be a qualified product by the quality control method, and a storage device using the outer packaging material for a storage device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic cross-sectional view showing an example of the laminated structure of the packaging material for a power storage device of the present invention.
[0023] Figure 2 This is a schematic cross-sectional view showing an example of the laminated structure of the packaging material for a power storage device of the present invention.
[0024] Figure 3 This is a schematic cross-sectional view showing an example of the laminated structure of the packaging material for a power storage device of the present invention.
[0025] Figure 4 This is a schematic cross-sectional view showing an example of the laminated structure of the packaging material for a power storage device of the present invention.
[0026] Figure 5 It is a schematic diagram which shows a plan view of the outer packaging material for an electric storage device of the present invention.
[0027] Figure 6 yes Figure 5 Schematic cross-sectional view along line AA′ of FIG. 1 (the stacking structure is omitted).
[0028] Figure 7 This is an image obtained by observing the curved surface portion of the formed electricity storage device packaging material obtained in Example 1 using a scanning electron microscope (SEM).
[0029] Figure 8 This is an image obtained by observing the curved surface portion of the formed electricity storage device packaging material obtained in Example 2 using a scanning electron microscope (SEM).
[0030] Fig. 9 This is an image obtained by observing the curved surface portion of the formed electricity storage device packaging material obtained in Example 3 using a scanning electron microscope (SEM).
[0031] Fig.10 This is an image obtained by observing the curved surface portion of the formed electricity storage device packaging material obtained in Example 6 using a scanning electron microscope (SEM).
[0032] Fig.11 This is a schematic diagram for explaining a method of housing an electric storage device element in a packaging body formed of the outer packaging material for an electric storage device of the present invention. DETAILED DESCRIPTION
[0033] The quality management of the present invention is a quality management method in a forming process of an outer packaging material for a storage device, characterized in that the quality management method takes the outer packaging material for a storage device as an object of quality management, the outer packaging material for a storage device is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside, the outer packaging material for a storage device is formed in a manner protruding from the heat-fusible resin layer side to the base layer side, and a recessed portion capable of accommodating a storage device element is formed on the heat-fusible resin layer side, and the quality management method includes a judgment step, in which the outer packaging material for a storage device to be inspected is extracted from the outer packaging material for a storage device with a recess formed therein, and the L of the reflected light is measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for the storage device to be inspected, respectively, under the measurement conditions of the SCI method, a field of view of 10°, and a light source F2. * a * b * L in color space * Value, based on L * The difference between the values of L and L can be used to determine whether the outer packaging material for a storage device having a recessed portion is a qualified product. * Whether the outer packaging material for a power storage device having a recessed portion is a qualified product can be determined by the size of the difference between the values.
[0034] The quality control method in the forming process of the outer packaging material for a storage device, the manufacturing method of the storage device, the outer packaging material for the storage device, and the storage device of the present invention are described in detail below. In this specification, the numerical range indicated by "to" means "above" or "below". For example, the expression of 2 to 15 mm means above 2 mm and below 15 mm.
[0035] 1. Quality management methods
[0036] The quality control method of the present invention is a quality control method in the molding process of the outer packaging material for storage devices. In the quality control method of the present invention, the outer packaging material for storage devices as the quality control object is composed of a laminated body having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside. The laminated structure of the outer packaging material for storage devices and the details of each layer are described later.
[0037] In the quality control method of the present invention, the outer packaging material for the storage device as the quality control object is formed in a manner protruding from the heat-fusible resin layer side to the base material layer side, and a recessed portion capable of accommodating the storage device element is formed on the heat-fusible resin layer side. That is, the outer packaging material for the storage device has a recessed portion formed by molding. As described later, the molding can be performed using a mold or the like.
[0038] The shape of the recess formed in the packaging material for a storage device is not particularly limited as long as it forms a space capable of accommodating the storage device element. Specific examples of the shape of the recess include a generally rectangular shape when viewed from the substrate layer 1 side and a generally circular shape when viewed from the substrate layer 1 side. Figure 5 , 6 The schematic diagram shows that a recessed portion 100 having a rectangular shape in plan view is provided in the outer packaging material 10 for an electric storage device. The rectangular shape in plan view includes not only the case where the corners of the rectangle are right angles, but also the case where Figure 5 , 6 The shapes shown have rounded shapes. For example, Figure 5 , 6 In the rectangular recessed portion in plan view as shown in the schematic diagram of , the curved surface portion 11 includes a corner portion 11a and a ridge portion 11b protruding toward the substrate layer 1 side, and the surfaces of the corner portion 11a and the ridge portion 11b on the substrate layer 1 side have a predetermined curvature radius R. The rectangular recessed portion 100 in plan view forms a rectangular parallelepiped space, in which the power storage device element is accommodated. When the shape of the recessed portion is a circular shape in plan view, the recessed portion forms a cylindrical space, in which the power storage device element is accommodated.
[0039] In addition, the size of the recess 100 is not particularly limited and can be appropriately designed according to the size of the power storage device (i.e., the size of the power storage device element to be stored). For example, when the shape of the recess is a rectangular shape in plan view, when the outer packaging material 10 for the power storage device is observed from the side of the substrate layer 1, the length of the long side of the recess 100 is, for example, about 20 mm or more, preferably about 30 mm or more, and more preferably about 50 mm or more. In addition, the length of the long side of the recess 100 is, for example, about 600 mm or less, preferably about 400 mm or less, and more preferably about 200 mm or less. As the preferred range of the length of the long side of the recess 100, 20 to 600 μm, 20 to 400 μm, 20 to 200 μm, 30 to 600 μm, 30 to 400 μm, 30 to 200 μm, 50 to 600 μm, 50 to 400 μm, and 50 to 200 mm can be listed. In addition, when the outer packaging material 10 for a storage device is observed from the side of the substrate layer 1, the length of the short side of the recess 100 is, for example, about 10 mm or more, preferably about 20 mm or more, and more preferably about 30 mm or more. In addition, the length of the short side of the recess 100 is, for example, about 300 mm or less, preferably about 200 mm or less, and more preferably about 100 mm or less. As a preferred range of the length of the short side of the recess 100, there can be cited 10 to 300 μm, 10 to 200 μm, 10 to 100 μm, 20 to 300 μm, 20 to 200 μm, 20 to 100 μm, 30 to 300 μm, 30 to 200 μm, and 30 to 100 mm. The length of the long side and the length of the short side of the recess 100 may be the same (that is, the shape of the recess 100 is a square shape when viewed from above).
[0040] In addition, the depth D of the recess 100 (see Figure 6 ) is not particularly limited and can be appropriately designed according to the size of the storage device (i.e., the size of the storage device element to be housed). For example, in the case of the storage device outer packaging material 10 having a total thickness described below, a thickness of 4 to 10 mm can be cited.
[0041] The recessed portion 100 of the outer packaging material 10 for a storage device is formed by molding a film-like outer packaging material for a storage device. Specifically, the laminate is molded (usually cold-formed) in a manner protruding from the thermally fusible resin layer 4 side to the substrate layer 1 side using a mold (female mold) disposed on the substrate layer 1 side of the laminate constituting the outer packaging material for a storage device and a mold (male mold) disposed on the thermally fusible resin layer 4 side, thereby forming the recessed portion 100 for accommodating the storage device element on the thermally fusible resin layer 4 side.
[0042] The quality control method of the present invention is characterized in that it includes a judgment step of judging whether the outer packaging material for a storage device having a recessed portion formed therein is a qualified product. In the judgment step, an outer packaging material for a storage device to be inspected is extracted from an outer packaging material for a storage device having a recessed portion 100 formed therein, and the L of reflected light is measured for the curved portion 11 and the non-curved portion 12 of the outer surface of the outer packaging material for the storage device to be inspected, which have the recessed portion formed therein, under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b * L in color space * Value, based on L * Whether the outer packaging material for the storage device with a recessed portion is a qualified product is determined by the size of the difference in the values. Where the quality management method of the present invention is used as a part of the manufacturing process of the storage device, the outer packaging material for the storage device to be inspected may be randomly or at a prescribed ratio (for example, 1 out of 1,000 to 10,000 outer packaging materials for storage devices with recessed portions is selected as the outer packaging material for the storage device to be inspected). Alternatively, all the outer packaging materials for storage devices with recessed portions may be selected as the outer packaging material for the storage device to be inspected. Wherein, in consideration of the production efficiency of the storage device, it is preferred to select L * The measurement of values etc. is automated and inserted into the production line.
[0043] As described above, by forming the recessed portion for housing the electric storage device element, a bent portion is formed in the outer packaging material for the electric storage device (see Figure 6 The curved surface portions 11, 13). In this curved portion, the outer packaging material for the storage device is stretched due to the forming, so the surface portion sometimes whitens. The whitening of the outer packaging material for the storage device due to the forming may lead to a poor appearance of the storage device, so it becomes the subject of quality management during the forming of the outer packaging material for the storage device. In this quality management, for example, in the case where the outer packaging material for the storage device is colored or the degree of whitening is serious, the presence or absence of whitening can be confirmed by visual inspection. However, the inventors of the present invention have found out through research that, in the curved portion of the outer packaging material for the storage device where the concave portion is formed, although it is difficult to confirm the whitening by visual inspection, sometimes very fine cracks are formed when the curved portion (the curved portion of the outer surface of the outer packaging material for the storage device) is observed using a scanning electron microscope or the like. Therefore, it is necessary to further improve the accuracy of the quality management method in the forming process of the outer packaging material for the storage device.
[0044] In the quality control method of the present invention, it is preferred that the curved surface portion of the concave portion formed by molding is based on L * The size of the difference between the values (i.e. L* Therefore, when the quality control method of the present invention is used in manufacturing power storage devices, L is appropriately set according to the quality required for the power storage device. * By using the evaluation criteria of the magnitude of the difference between the two values, it is possible to appropriately suppress the production of defective products in the molding step of the outer packaging material for a storage device.
[0045] About L * The evaluation criteria of the difference between the L and L values of the curved surface 11 can be appropriately set according to the quality required of the power storage device. For example, from the perspective of managing the whitening of the curved surface 11, the L value of the curved surface 11 can be set to * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the two (the absolute value of the difference for judging a qualified product) is preferably 2.0 or less, more preferably 1.8 or less, further preferably 1.5 or less, further preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * Preferred ranges of the absolute value of the difference between the values include about 0.0 to 2.0, about 0.0 to 1.8, about 0.0 to 1.5, about 0.0 to 1.0, about 0.0 to 0.5, and about 0.0 to 0.3.
[0046] When forming the recessed portion of the outer packaging material for a storage device, the greatest strain is applied to the curved portion, which easily generates micro cracks. For example, cracks form gaps in the layers constituting the outer packaging material for a storage device, such as the surface coating layer, exposing the gloss of the base. The L of the curved portion is larger than that of the non-curved portion. * For example, even if the outer packaging material for a storage device has excellent electrolyte resistance, once microcracks appear on the curved surface formed by molding, the electrolyte will penetrate through the microcracks, causing the outer packaging material to peel off. * In the design of the outer packaging material for storage devices with a small difference in the value, a hard outer packaging material for storage devices cannot follow the molding and cracks are generated, so it is adjusted to have the characteristics of being hard but soft and elastic. In addition, although the outer packaging material for storage devices is hard and elastic, when there are a large amount of additives such as wax or particles, the adhesion between the boundaries of the resin and the particles, or between the resin and the wax is weak, and cracks are easily generated from the boundaries, so it is preferable to adjust the content of the additives to the necessary minimum.
[0047] In addition, in the power storage device, for example, if fine cracks are formed in the curved portion 11 of the power storage device outer packaging material 10, depending on the extent of the cracks, when the electrolyte adheres to the surface of the power storage device outer packaging material during the manufacturing process of the power storage device, the electrolyte may penetrate the cracks and cause peeling between the layers constituting the power storage device outer packaging material. From the perspective of quality control to manufacture power storage devices with excellent electrolyte resistance, in the judgment process, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values (the absolute value of the difference for judging a qualified product) is preferably managed under stricter conditions than the above-mentioned whitening, and is preferably 1.5 or less, more preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is greater than 0.0. * The value is the same as the L of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is 0.0 to 1.5, 0.0 to 1.0, 0.0 to 0.5, and 0.0 to 0.3. * The value is the same as a of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values (i.e., the absolute value of the difference for judging a qualified product) is about 0.00 to 0.12. * Value and b of the non-curved surface * The preferred range of the absolute value of the difference between the values (i.e., the absolute value of the difference for judging a qualified product) is about 0.00 to 0.60. * The value of ab is preferably about 1.8 or less, more preferably about 1.0 or less. * Preferred ranges of the value of ab include about 0.0 to 1.8 and about 0.0 to 1.0. * The value of ab can be based on the formula ΔE * ab=[(ΔL) 2 +(Δa) 2 +(Δb) 2 ] 1 / 2 calculate.
[0048] In the present invention, the determination step can be specifically implemented as follows. The curved portion 11 of the outer surface of the substrate layer 1 side forming the recess 100 of the outer packaging material for storage devices, that is, the curved portion 11 protruding toward the substrate layer 1 side of the outer packaging material 10 for storage devices and the non-curved portion 12 of the outer surface of the substrate layer 1 side forming the recess 100 ( Figure 5 , 6 The non-curved surface portion 12) shown in the schematic diagram is measured under the following conditions * a * b * L in color space * The observation conditions of a spectrophotometer (e.g., spectrophotometer (CM-700d) manufactured by Konica Minolta) calibrated with a white calibration plate (e.g., CM-A177 manufactured by Konica Minolta) are set to 10°, the observation light source is set to F2, and the SCI mode (JIS Z8722-2009) is set. Next, the L values of the outer surfaces (surfaces on the substrate layer 1 side) of the curved surface 11 and the non-curved surface 12 to be measured are measured at room temperature and humidity. * The measurement diameter of the curved surface 11 was set to 8 mmφ, and the measurement diameter of the non-curved surface 12 was set to 3 mmφ, and the measurement was performed. * Value and b * The values are also related to L * Measurement of the values is also performed under the measurement conditions.
[0049] As L * The curved surface portion 11 to be measured for the value of L is the portion of the curved surface portion 11 that forms the recess 100 that is most stretched due to molding (molding when forming the recess 100) (i.e., the portion that is most likely to generate fine cracks). The most stretched portion is the above-mentioned L * The part with the largest difference in value is the L of the curved surface 11. * The part with the largest value. Figure 5 , 6 When the rectangular concave portion 100 is viewed from above as shown in the schematic diagram of FIG. 1 , the corner 11a of the curved surface portion 11 (rectangular shape when viewed from above) becomes the most stretched portion, so it is suitable to use the corner 11a as the L * The object of measurement of the value. Among them, there are four corners 11a in the shape of the forming mold. If the shapes of the four corners of the mold forming the corners 11a are the same, then the L of the corner 11a * The values are also substantially the same, so if L is measured at the corner 11a at 1 * value, L for the other three corners 11a can be omitted * Measurement of a value. * Value and b* The value of the curved surface 11 and the measured L * The curved surface portion 11 of the value is the same.
[0050] In addition, depending on the shape of the mold, etc., even if Figure 5 , 6 In the rectangular concave portion in top view shown in the schematic diagram of FIG. 1 , the ridge portion 11b protruding toward the substrate layer 1 side in the curved surface portion 11 may become the most stretched portion. For example, in the case where the curvature radius R of the ridge portion 11b is smaller than the curvature radius R of the corner portion 11a on the surface on the substrate layer 1 side, the ridge portion 11b protruding toward the substrate layer 1 side in the curved surface portion 11 may become the most stretched portion. In this case, it is appropriate to use the ridge portion 11b as L * In addition, if the concave part is circular in plan view, for example, there is no corner, so the ridgeline is taken as L. * The measurement object of the value. Figure 6 The curved surface portion 13 is a curved surface portion that does not protrude toward the substrate layer 1 side. Compared with the curved surface portion 11 that protrudes toward the substrate layer 1 side, the stretching caused by molding is usually smaller. * The curved surface portion 11 of the measurement object of the value may be used or may not be used.
[0051] In addition, the L of the non-curved surface * The L value is preferably measured with the portion that is substantially not stretched by forming as the non-curved portion 12. * The value is usually the same at any position, but when the recess 100 is viewed from the substrate layer 1 side, for example, it is preferable to measure L with the center of the recess 100 as the non-curved surface portion 12. * value.
[0052] In the quality control method of the present invention, the L of the curved surface portion 11 of the power storage device packaging material 10 to be quality controlled is * The value and L of the non-curved surface 12 * The values are not particularly limited, and these L values can be appropriately managed from the viewpoints of whitening and electrolyte resistance as described above. * For example, when the outer packaging material 10 for a storage device is colored (specifically, when the outer packaging material 10 for a storage device is observed from the side of the substrate layer 1, a color different from that of the barrier layer 3 is observed because at least one layer (for example, the substrate layer 1, the adhesive layer 2, the coloring layer, the surface covering layer 6, etc. described later) of the outer packaging material 10 for a storage device is colored, the whitening of the curved portion 11 and the like are easily judged as defective products. In particular, when the outer packaging material 10 for a storage device is dark in appearance such as black, the quality management method of the present invention is preferably adopted.
[0053] From this point of view, the L of the non-curved surface portion 12 of the power storage device packaging material 10 to be the subject of quality control is * The value is preferably about 60.0 or less, more preferably about 50.0 or less, further preferably about 40.0 or less, and further preferably about 30.0 or less. * The value is, for example, about 0.0 or more, about 10.0 or more, about 20.0 or more, etc. * Preferred ranges of the value include 0.0 to 60.0, 0.0 to 50.0, 0.0 to 40.0, 0.0 to 30.0, 10.0 to 60.0, 10.0 to 50.0, 10.0 to 40.0, 10.0 to 30.0, 20.0 to 60.0, 20.0 to 50.0, 20.0 to 40.0, and 20.0 to 30.0. Similarly, the a of the non-curved surface portion 12 is * The value is, for example, about +2.00 or less, preferably about +1.00 or less. * The value is, for example, about -2.00 or more, preferably about -1.00 or more. * Preferred ranges of the value include -2.00 to +2.00, -2.00 to +1.00, -1.00 to +2.00, and -1.00 to +1.00. * The value is, for example, approximately +1.00 or less, preferably approximately +0.00 or less. * The value is, for example, about -3.00 or more, preferably about -2.00 or more. * Preferred ranges of the value include -3.00 to +1.00, -3.00 to +0.00, -2.00 to +1.00, and -2.00 to +0.00.
[0054] Regarding L of curved surface 11 * The value is the same as the L of the non-curved surface 12 * The difference in the values can be adjusted to a predetermined value by, for example, adjusting the composition, thickness, etc. of the outermost layer (e.g., the base material layer 1 and the surface covering layer 6 described later) of the outer packaging material 10 for storage devices, or the shape, size, surface roughness, etc. of the mold, and the pressing pressure of the mold. In addition, as described later, the L value of the curved portion 11 can also be adjusted by adjusting the lamination conditions of each layer in the lamination process of the outer packaging material 10 for storage devices. * The value is the same as the L of the non-curved surface 12 * The difference in value.
[0055] In addition, for example, when the outer packaging material for storage devices is matte style, the whitening of the curved surface 11 is easily judged as a defective product, so it is preferred to adopt the quality management method of the present invention. From this point of view, the mirror glossiness of the non-curved surface 12 of the outer packaging material 10 for storage devices as the object of quality management is preferably, for example, about 5.0 or less, and more preferably about 3.6 or less. And, the mirror glossiness is, for example, about 1.0 or more. As the preferred range of the mirror glossiness, 1.0 to 5.0 and 1.0 to 3.6 can be listed. The mirror glossiness of the non-curved surface 12 of the outer packaging material 10 for storage devices is determined as described below. Among them, the mirror gloss of the non-curved portion of the outer packaging material for a storage device with a recess formed therein is substantially the same as the mirror gloss of the outer surface of the outer packaging material for a storage device before forming (the position that becomes the non-curved portion after forming) (that is, the mirror gloss of the non-curved portion will not substantially change due to forming. For example, when observing the recess 100 from the side of the substrate layer 1, it is preferred to measure the mirror gloss with the center part of the recess 100 as the non-curved portion 12). Therefore, when the outer packaging material for a storage device before forming can be obtained, the mirror gloss of the outer surface of the outer packaging material for a storage device before forming can be measured by the following measurement method.
[0056] <Measurement of specular gloss>
[0057] The specular glossiness of the outer surface of the non-curved portion of the outer packaging material for a storage device is measured by the following measurement method. According to the method specified in JIS Z 8741 (1997), a gloss meter (for example, a gloss meter micro-tri-gloss (measurement area 9 mm×15 mm) manufactured by Toyo Seiki Seisaku-sho) is used to measure the specular glossiness of the surface coating layer at an incident angle of 60 degrees.
[0058] As described above, the quality control method of the present invention is a novel quality control method, which includes L-shaped parts based on the curved surface part and the non-curved surface part forming the concave part in the molding process of the outer packaging material for the storage device. *The judgment process of judging whether the outer packaging material for a storage device having a recess formed therein is a qualified product by the size of a value can also perform quality management with higher accuracy compared with the existing quality management by visual inspection or using a camera. Therefore, by using the quality management method of the present invention when manufacturing storage devices, qualified storage devices can be manufactured efficiently. In the judgment process, for example, the characteristics (forming characteristics) of the outer packaging material for the storage device are evaluated based on whether the outer packaging material for the storage device has fine cracks formed in the layer constituting the outer packaging material for the storage device due to the forming when the recess is formed. This can be used as a judgment method. By using this judgment method, the characteristics of the outer packaging material for the storage device can be simply evaluated without using a scanning electron microscope or the like.
[0059] 2. Method for manufacturing power storage device
[0060] The method for manufacturing an electric storage device of the present invention is a method for manufacturing an electric storage device in which an electric storage device element is sealed by a packaging body, wherein the packaging body is formed by sealing an outer packaging material 10 for an electric storage device, which is composed of a laminate having at least a base layer 1, a barrier layer 3 and a heat-fusible resin layer 4 in this order from the outside. Figure 5 , 6 The heat-fusible resin layer 4 is formed by heat-melting the peripheral edge 14) of the storage device. The manufacturing method of the storage device of the present invention utilizes the quality management method described in the above-mentioned "1. Quality management method" when manufacturing the storage device, and the description of repeated matters is appropriately omitted. In addition, the stacked structure of the outer packaging material for the storage device as described above and the details of each layer are described later.
[0061] The method for manufacturing an electric storage device of the present invention includes a step of preparing an outer packaging material for an electric storage device having a recessed portion formed therein, wherein the outer packaging material for an electric storage device having a recessed portion accommodates an electric storage device element in a manner that protrudes from the heat-fusible resin layer side of the outer packaging material for an electric storage device toward the base material layer side. The outer packaging material for an electric storage device having a recessed portion is as described in the above-mentioned "1. Quality management method", and a description thereof is omitted.
[0062] In addition, the manufacturing method of the electric storage device of the present invention includes a determination step, in which an outer packaging material for an electric storage device to be inspected is extracted from an outer packaging material for an electric storage device having a recessed portion formed therein, and the L of reflected light is measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for the electric storage device to be inspected, respectively, under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b * L in color space * Value, based on L *The size of the difference between the values is used to judge whether the outer packaging material for the storage device with the recessed portion is a qualified product. Regarding the judgment process, it is also as described in the above-mentioned "1. Quality management method", and the description is omitted. Among them, in the judgment process of the manufacturing method of the storage device of the present invention, when the outer packaging material for the storage device with the recessed portion is judged to be a defective product, the stacking process of the outer packaging material for the storage device or the forming process of the outer packaging material for the storage device is returned to adjust the composition, stacking method, forming conditions, etc. of the outer packaging material for the storage device until it is judged to be a qualified product in the judgment process.
[0063] The manufacturing method of the electric storage device of the present invention includes the steps of housing an electric storage device element in a recessed portion of an outer packaging material for an electric storage device and manufacturing the electric storage device. In the manufacturing method of the electric storage device of the present invention, when the outer packaging material for an electric storage device having a recessed portion is judged to be a qualified product as a result of the judging step, it is judged that the formation of the recessed portion is appropriate, housing the electric storage device element in the recessed portion, and manufacturing the electric storage device.
[0064] As described above, L can be adjusted according to the quality required of the power storage device. * The evaluation criteria of the difference in L values is appropriately set. For example, from the perspective of managing the whitening of the curved surface portion 11, the L value of the curved surface portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values (the absolute value of the difference for judging a qualified product) is preferably 2.0 or less, more preferably 1.8 or less, further preferably 1.5 or less, further preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * Preferred ranges of the absolute value of the difference between the values include about 0.0 to 2.0, about 0.0 to 1.8, about 0.0 to 1.5, about 0.0 to 1.0, about 0.0 to 0.5, and about 0.0 to 0.3.
[0065] In addition, as described above, from the viewpoint of quality control to manufacture a power storage device with excellent electrolyte resistance, in the determination step, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values (the absolute value of the difference for judging a qualified product) is preferably managed under stricter conditions than the above-mentioned whitening, and is preferably 1.5 or less, more preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is greater than 0.0. * The value is the same as the L of the non-curved surface 12* The preferred range of the absolute value of the difference between the values is 0.0 to 1.5, 0.0 to 1.0, 0.0 to 0.5, and 0.0 to 0.3. * The value is the same as a of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values (i.e., the absolute value of the difference for judging a qualified product) is about 0.00 to 0.12. * Value and b of the non-curved surface * A preferred range of the absolute value of the difference between the values (that is, the absolute value of the difference for determining a non-defective product) is about 0.00 to 0.60.
[0066] A known method can be applied to the method of manufacturing the electric storage device by accommodating the electric storage device element in the recess 100. Specifically, the electrodes, electrolyte, etc. constituting the electric storage device element are accommodated in the recess 100, and the heat-fusible resin layers 4 of the outer packaging material 10 for the electric storage device are heat-fused to each other, thereby sealing the electric storage device element and obtaining the electric storage device.
[0067] 3. Inspection method
[0068] The inspection method of the present invention is an inspection method for an outer packaging material for a storage device having a recessed portion formed therein. The inspection method of the present invention takes the outer packaging material for a storage device as an inspection object, and the outer packaging material for a storage device is composed of a laminate having at least a base layer, a barrier layer, and a heat-fusible resin layer in order from the outside, and the outer packaging material for a storage device is formed in a manner protruding from the heat-fusible resin layer side to the base layer side, and a recess capable of accommodating a storage device element is formed on the heat-fusible resin layer side. The above-mentioned quality management method of the present invention can be said to be a quality management method utilizing the inspection method of the present invention, and the description of matters that are repeated with those described in the above-mentioned "1. Quality management method" is appropriately omitted. In addition, the stacked structure of the outer packaging material for a storage device as described above and the details of each layer are described later.
[0069] In the inspection method of the present invention, the outer packaging material for a power storage device having a recessed portion formed therein, which is the inspection target, is as described in the above-mentioned section “1. Quality management method”, and a description thereof is omitted.
[0070] The inspection method of the present invention includes a determination step in which the L of reflected light is measured for the curved portion and the non-curved portion of the outer surface of the storage device packaging material having the recess formed thereon under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b *L in color space * Value, based on L * The size of the difference between the values is used to determine whether the outer packaging material for a storage device having a recessed portion is a qualified product. The determination process is the same as that described in the above-mentioned "1. Quality management method" and its description is omitted.
[0071] As described above, L can be adjusted according to the quality required of the power storage device. * The evaluation criteria of the difference in L values is appropriately set. For example, from the perspective of managing the whitening of the curved surface portion 11, the L value of the curved surface portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values (the absolute value of the difference for judging a qualified product) is preferably 2.0 or less, more preferably 1.8 or less, further preferably 1.5 or less, further preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * Preferred ranges of the absolute value of the difference between the values include about 0.0 to 2.0, about 0.0 to 1.8, about 0.0 to 1.5, about 0.0 to 1.0, about 0.0 to 0.5, and about 0.0 to 0.3.
[0072] In addition, as described above, from the viewpoint of quality control to manufacture a power storage device with excellent electrolyte resistance, in the determination step, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values (the absolute value of the difference for judging a qualified product) is preferably managed under stricter conditions than the above-mentioned whitening, and is preferably 1.5 or less, more preferably 1.0 or less, further preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is greater than 0.0. * The value is the same as the L of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is 0.0 to 1.5, 0.0 to 1.0, 0.0 to 0.5, and 0.0 to 0.3. * The value is the same as a of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values (i.e., the absolute value of the difference for judging a qualified product) is about 0.00 to 0.12. * Value and b of the non-curved surface *A preferred range of the absolute value of the difference between the values (that is, the absolute value of the difference for determining a non-defective product) is about 0.00 to 0.60.
[0073] 4. Outer packaging materials for power storage devices
[0074] The outer packaging material 10 for a storage device of the present invention is an outer packaging material for a storage device composed of a laminated body having at least a base layer 1, a barrier layer 3 and a heat-fusible resin layer 4 in order from the outside. The outer packaging material 10 for a storage device is formed in a manner protruding from the heat-fusible resin layer 4 side to the base layer 1 side, and has a recess 100 for accommodating a storage device element on the heat-fusible resin layer 4 side. And, it is characterized in that, for the curved portion 11 and the non-curved portion 12 of the outer surface forming the recess of the outer packaging material 10 for a storage device, the L of the reflected light is measured under the measurement conditions of the SCI method, the field of view 10° and the light source F2. * a * b * L in color space * When the value is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference is 1.5 or less. That is, the outer packaging material 10 for a storage device of the present invention is the outer packaging material 10 for a storage device described in the above "1. Quality Management Method" wherein the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * Therefore, the description of the shape and the like of the packaging material 10 for a power storage device will be omitted.
[0075] As described above, in an electric storage device, once fine cracks are formed on the curved surface of the outer packaging material for an electric storage device, depending on the extent of the cracks, when an electrolyte adheres to the surface of the outer packaging material for an electric storage device during the manufacturing process of the electric storage device, the electrolyte may penetrate the cracks, causing peeling between the layers constituting the outer packaging material for an electric storage device. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is preferably controlled under stricter conditions than the above-mentioned whitening. From this point of view, in the outer packaging material 10 for a storage device of the present invention, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is set to a particularly low value of 1.5 or less. In the outer packaging material 10 for a storage battery device of the present invention, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 *The absolute value of the difference between the values is preferably 1.0 or less, more preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is greater than 0.0. * The value is the same as the L of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is 0.0 to 1.5, 0.0 to 1.0, 0.0 to 0.5, and 0.0 to 0.3. * The value is the same as a of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is about 0.00 and 0.12. * Value and b of the non-curved surface * The preferred range of the absolute value of the difference between the values is about 0.00 and 0.60. * Value, a * Value and b * The values, their measurement methods, and details of the measurement locations are as described in the above "1. Quality Management Methods".
[0076] In addition, in the present invention, regarding the outer packaging material 10 for a storage device before the recess 100 is formed, the outer packaging material for a storage device is formed under the following molding conditions in a manner that it protrudes from the heat-fusible resin layer 4 side to the base material layer 1 side, and a recess for accommodating the storage device element is formed on the heat-fusible resin layer 4 side. For the curved portion 11 and the non-curved portion 12 of the outer surface of the outer packaging material 10 for the storage device forming the recess, the L values of the reflected light are measured under the measurement conditions of the SCI method, the field of view 10°, and the light source F2. * a * b * L in color space * In the case of a value of * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference is less than 1.5. The outer packaging material 10 for the storage device does not form the above-mentioned concave portion. When the concave portion is formed under the prescribed molding conditions, the L of the curved portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference is less than 1.5.
[0077] (forming conditions)
[0078] The outer packaging material for the storage device is arranged between a forming die (female die) having a diameter of 54.5 mm (TD) × 31.6 mm (MD) and a corresponding forming die (male die) in such a way that the female die side is located on the substrate layer side, and the pressing pressure (surface pressure) is set to 0.25 MPa, and cold forming is performed with a forming depth of 3.0 mm to form a concave portion in a rectangular shape when viewed from above. The gap between the female die and the male die is set to 0.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the surface roughness standard sheet for comparison in JIS B 0659-1:2002 Annex 1 (reference) of the surface of the female die is 0.8 μm. The corner R of the female die is 2.0 mm, and the ridge R is 2.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the surface roughness standard sheet for comparison in JIS B 0659-1:2002 Annex 1 (reference) of the surface of the male die is 3.2 μm. The corner R of the male mold was 2.0 mm, and the ridge R was 2.0 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Annex 1 (reference) of the male mold corner R and ridge R was 1.6 μm.
[0079] In the packaging material 10 for a storage device before molding, after the recessed portion is formed under the above molding conditions, the L of the curved surface portion 11 is * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is preferably 1.0 or less, more preferably 0.5 or less, and particularly preferably 0.3 or less. * The value is the same as the L of the non-curved surface 12 * The absolute value of the difference between the values is greater than 0.0. * The value is the same as the L of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is 0.0 to 1.5, 0.0 to 1.0, 0.0 to 0.5, and 0.0 to 0.3. * The value is the same as a of the non-curved surface 12 * The preferred range of the absolute value of the difference between the values is about 0.00 and 0.12. * Value and b of the non-curved surface * The preferred range of the absolute value of the difference between the values is about 0.00 and 0.60. * Value, a * Value and b * The values, their measurement methods, and details of the measurement locations are as described in the above "1. Quality Management Methods".
[0080] Laminated structure of packaging material for power storage device
[0081] For example, the outer packaging material 10 for an electric storage device Figure 1 As shown, it is composed of a laminated body having at least a base material layer 1, a barrier layer 3 and a heat-fusible resin layer 4 in this order. In the outer packaging material 10 for a storage device, the base material layer 1 is the outermost layer, and the heat-fusible resin layer 4 is the innermost layer. When assembling a storage device using the outer packaging material 10 for a storage device and a storage device element, the storage device element is accommodated in a space formed by heat-fusing the peripheral edge 14 of the heat-fusible resin layer 4 of the outer packaging material 10 for the storage device in a state where the heat-fusible resin layer 4 is opposite to each other. In the laminated body constituting the outer packaging material 10 for a storage device of the present invention, with the barrier layer 3 as a reference, the heat-fusible resin layer 4 side is on the inner side than the barrier layer 3, and the base material layer 1 side is on the outer side than the barrier layer 3.
[0082] For example, the outer packaging material 10 for an electric storage device Figures 2 to 4 As shown, between the substrate layer 1 and the barrier layer 3, an adhesive layer 2 may be provided as required for the purpose of improving the adhesion between these layers. Figure 3 and Figure 4 As shown in FIG. 1 , an adhesive layer 5 may be provided between the barrier layer 3 and the heat-fusible resin layer 4 as required for the purpose of improving the adhesion between these layers. Figure 4 As shown, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the thermally fusible resin layer 4 side) as necessary.
[0083] The thickness of the laminate constituting the outer packaging material 10 for a storage device is not particularly limited, but preferably, from the viewpoint of reducing costs and improving energy density, it is about 180 μm or less, about 155 μm or less, or about 120 μm or less. In addition, from the viewpoint of maintaining the function of the outer packaging material for a storage device to protect the storage device element, the thickness of the laminate constituting the outer packaging material 10 for a storage device is preferably about 35 μm or more, about 45 μm or more, or about 60 μm or more. In addition, the preferred range of the laminate constituting the outer packaging material 10 for a storage device is, for example, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 180 μm, about 60 to 155 μm, about 60 to 120 μm, and particularly preferably about 60 to 155 μm.
[0084] In the outer packaging material 10 for a storage device, the ratio of the total thickness of the base material layer 1, the adhesive layer 2 provided as required, the barrier layer 3, the adhesive layer 5 provided as required, the heat-fusible resin layer 4, and the surface coating layer 6 provided as required is preferably 90% or more, more preferably 95% or more, and further preferably 98% or more, relative to the thickness (total thickness) of the laminate constituting the outer packaging material 10 for a storage device. As a specific example, when the outer packaging material 10 for a storage device of the present invention includes the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, and the heat-fusible resin layer 4, the ratio of the total thickness of these layers is preferably 90% or more, more preferably 95% or more, and further preferably 98% or more, relative to the thickness (total thickness) of the laminate constituting the outer packaging material 10 for a storage device. In addition, when the outer packaging material 10 for the storage device of the present invention is a laminate including a base material layer 1, an adhesive layer 2, a barrier layer 3 and a thermally fusible resin layer 4, the ratio of the total thickness of these layers to the thickness of the laminate constituting the outer packaging material 10 for the storage device is, for example, 80% or more, preferably 90% or more, more preferably 95% or more, and further preferably 98% or more.
[0085] [Base material layer 1]
[0086] In the present invention, the base material layer 1 is a layer provided for the purpose of exerting a function as a base material of the outer packaging material for a power storage device, etc. The base material layer 1 is located on the outer layer side of the outer packaging material for a power storage device.
[0087] There is no particular limitation on the material for forming the base material layer 1 as long as it has a function as a base material, that is, at least insulating properties. The base material layer 1 can be formed using, for example, a resin, and the resin may contain additives described below.
[0088] When the substrate layer 1 is formed of a resin, the substrate layer 1 may be, for example, a resin film formed of a resin, or may be formed by coating a resin. The resin film may be an unstretched film or a stretched film. As a stretched film, a uniaxially stretched film and a biaxially stretched film may be cited, preferably a biaxially stretched film. As a stretching method for forming a biaxially stretched film, for example, a sequential biaxial stretching method, an inflation method, a simultaneous biaxial stretching method, etc. may be cited. As a method for coating a resin, a roll coating method, a gravure coating method, an extrusion coating method, etc. may be cited.
[0089] Examples of the resin forming the substrate layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin and the like, or modified products of these resins. The resin forming the substrate layer 1 may be a copolymer of these resins, or a modified product of a copolymer. Furthermore, it may be a mixture of these resins.
[0090] As the resin forming the base material layer 1, polyester and polyamide are preferred among them.
[0091] As polyester, specifically, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolyester, etc. can be mentioned. In addition, as copolyester, copolyester with ethylene terephthalate as the main body of repeating unit can be mentioned. Specifically, copolymer polyester (hereinafter abbreviated as polyethylene (terephthalate / isophthalic acid)) with ethylene terephthalate as the main body of repeating unit and polymerized with ethylene isophthalate can be mentioned, polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. can be mentioned. These polyesters may be used alone or in combination of two or more.
[0092] In addition, specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid; and polyamide MXD6 Aromatic polyamides such as poly(m-xylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides obtained by copolymerizing a lactam component and an isocyanate component such as 4,4′-diphenylmethane-diisocyanate; polyesteramide copolymers and / or polyetheresteramide copolymers of copolymerized polyamides and polyesters and / or polyalkylene ether glycols; and copolymers thereof. These polyamides may be used alone or in combination of two or more.
[0093] The substrate layer 1 preferably comprises at least one of a polyester film, a polyamide film and a polyolefin film, preferably comprises at least one of a stretched polyester film, a stretched polyamide film and a stretched polyolefin film, more preferably comprises at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film and a stretched polypropylene film, and further preferably comprises at least one of a biaxially stretched polyethylene terephthalate film, a biaxially stretched polybutylene terephthalate film, a biaxially stretched nylon film and a biaxially stretched polypropylene film.
[0094] The substrate layer 1 may be a single layer or may be composed of two or more layers. When the substrate layer 1 is composed of two or more layers, the substrate layer 1 may be a laminated body formed by laminating resin films with an adhesive or the like, or a laminated body formed by co-extruding resins to form two or more layers of resin films. In addition, a laminated body formed by co-extruding resins to form two or more layers of resin films may be used directly as the substrate layer 1 in an unstretched state, or may be formed by uniaxial stretching or biaxial stretching.
[0095] In the substrate layer 1, as specific examples of a laminate of two or more layers of resin films, there can be mentioned a laminate of a polyester film and a nylon film, a laminate of two or more layers of nylon films, a laminate of two or more layers of polyester films, etc., preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more layers of stretched nylon films, and a laminate of two or more layers of stretched polyester films. For example, when the substrate layer 1 is a laminate of two layers of resin films, preferably a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film, more preferably a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film. Furthermore, since polyester resin is less likely to be discolored when an electrolyte solution adheres to the surface, when the base layer 1 is a laminate of two or more resin films, the polyester resin film is preferably located as the outermost layer of the base layer 1 .
[0096] In the case where the substrate layer 1 is a laminate of two or more layers of resin films, the two or more layers of resin films can be laminated via an adhesive. As for the preferred adhesive, the same adhesive as the adhesive exemplified in the adhesive layer 2 described later can be cited. Among them, as a method for laminating two or more layers of resin films, there is no particular restriction, and a known method can be adopted, such as dry lamination, sandwich lamination, extrusion lamination, hot lamination, etc., and dry lamination can be cited as a preferred method. In the case of lamination by dry lamination, a polyurethane adhesive is preferably used as the adhesive. At this time, as the thickness of the adhesive, for example, 2 to 5 μm can be cited. In addition, an anchor coating can also be formed and laminated on the resin film. The anchor coating can cite the same substance as the adhesive exemplified in the adhesive layer 2 described later. At this time, as the thickness of the anchor coating, for example, 0.01 to 1.0 μm can be cited.
[0097] In addition, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the inside of the base layer 1. The additives may be used alone or in combination of two or more.
[0098] In the present invention, from the viewpoint of improving the formability of the outer packaging material for storage devices, it is preferred that a lubricant is present on the surface of the substrate layer 1. As a lubricant, there is no particular limitation, and preferred amide lubricants can be cited. As specific examples of amide lubricants, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethylamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, aromatic bisamides, etc. can be cited. As specific examples of saturated fatty acid amides, lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, hydroxystearic acid amides, etc. can be cited. As specific examples of unsaturated fatty acid amides, oleic acid amides, erucic acid amides, etc. can be cited. As specific examples of substituted amides, N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, N-stearyl erucic acid amides, etc. can be cited. In addition, as specific examples of hydroxymethylamides, hydroxymethyl stearic acid amides, etc. can be cited. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipamide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearic acid stearamide ethyl ester, etc. Specific examples of the aromatic bisamide include meta-xylylene bisstearic acid amide, meta-xylylene bishydroxystearic acid amide, N,N′-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more.
[0099] When a lubricant is present on the surface of the substrate layer 1, the amount thereof is not particularly limited, but is preferably about 3 mg / m 2 More preferably 4 to 15 mg / m 2 The degree is more preferably 5 to 14 mg / m 2 degree.
[0100] The lubricant present on the surface of the base layer 1 may be a lubricant that is caused to seep out of the lubricant contained in the resin constituting the base layer 1 , or may be a lubricant that is coated on the surface of the base layer 1 .
[0101] The thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and can be, for example, about 3 to 50 μm, preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more layers of resin films, the thickness of the resin films constituting each layer can be preferably about 2 to 25 μm.
[0102] [Adhesive layer 2]
[0103] In the packaging material for a power storage device of the present invention, the adhesive layer 2 is a layer provided between the base layer 1 and the barrier layer 3 as necessary in order to improve the adhesion between them.
[0104] The adhesive layer 2 is formed of an adhesive capable of bonding the substrate layer 1 and the barrier layer 3. The adhesive used in forming the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a heat-melting type, a hot pressing type, and the like. In addition, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not accompany a curing reaction. In addition, the adhesive layer 2 may be a single layer or a multilayer.
[0105] As the adhesive component contained in the adhesive, specifically, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolyesters can be cited; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolyamides; polyolefin resins such as polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth) acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone resins, etc. These adhesive components can be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the resins forming these adhesive components can be used together with a suitable curing agent to improve the bonding strength. The curing agent can be selected from polyisocyanates, multifunctional epoxy resins, polymers containing oxazoline groups, polyamine resins, acid anhydrides, etc. according to the functional groups possessed by the adhesive components.
[0106] As polyurethane adhesives, for example, polyurethane adhesives containing a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. Polyols such as polyester polyols, polyether polyols and acrylic polyols can be cited as main agents, and polyisocyanates of aromatic or aliphatic types can be cited as two-component curing polyurethane adhesives. In addition, as polyol compounds, polyester polyols having hydroxyl groups in the side chains in addition to the hydroxyl groups at the ends of the repeating units are preferably used. As curing agents, aliphatic, alicyclic, aromatic, and aromatic aliphatic isocyanate compounds can be cited. As isocyanate compounds, for example, hexamethylene diisocyanate (HDI), xylene diisocyanate (XDI), isophorone diisocyanate (IPDI), hydrogenated XDI (H6XDI), hydrogenated MDI (H12MDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), etc. can be cited. And, can enumerate the polyfunctional isocyanate modified body etc. of 1 or more kinds derived from these diisocyanates.In addition, can also use polymer (for example trimer) as polyisocyanate compound.These polymers can enumerate adduct, biuret body, isocyanurate body etc..By adhesive layer 2 is formed by polyurethane adhesive, can give storage device outer packaging material with excellent electrolyte resistance, even if electrolyte is attached to the side, can also suppress substrate layer 1 peeling.
[0107] In addition, adhesive layer 2 allows to add other components within the limit of not hindering adhesion, and can contain colorant or thermoplastic elastomer, tackifier, filler (comprising particles) etc. Containing colorant through adhesive layer 2, storage device can be colored with outer packaging material. As colorant, known colorants such as pigment, dye can be used. In addition, colorant can only use 1 kind, also can mix and use more than 2 kinds.
[0108] As described above, for example, when the outer packaging material 10 for a storage device is colored (specifically, when the outer packaging material 10 for a storage device is observed from the side of the substrate layer 1, a color different from that of the barrier layer 3 is recognized because at least one layer (for example, the substrate layer 1, the adhesive layer 2, the colored layer, the surface covering layer 6, etc. described later) of the outer packaging material 10 for a storage device is colored, the curved portion 11 is easily judged as a defective product due to whitening, etc., and the quality control method of the present invention is effective, especially when the outer packaging material 10 for a storage device is a dark color such as black. Therefore, it is preferred that the adhesive layer 2 of the outer packaging material 10 for a storage device is colored.
[0109] The type of pigment is not particularly limited as long as it is within the range that does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo pigments, phthalocyanine pigments, quinacridone pigments, anthraquinone pigments, dioxazine pigments, indigo thioindigo pigments, perinone-perylene pigments, isoindoline pigments, benzimidazolone pigments, and inorganic pigments include carbon black pigments, titanium oxide pigments, cadmium pigments, lead pigments, chromium oxide pigments, iron pigments, and fine powder of mica, fish scale foil, and the like.
[0110] Among the coloring agents, carbon black is preferred in order to make the appearance of the packaging material for a power storage device black, for example.
[0111] The average particle size of the pigment is not particularly limited, and may be, for example, about 0.05 to 5 μm, preferably about 0.08 to 2 μm. The average particle size of the pigment is a median diameter measured by a laser diffraction / scattering particle size distribution measuring device.
[0112] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the power storage device packaging material can be colored, and may be, for example, about 5 to 60% by mass, preferably 10 to 40% by mass.
[0113] The thickness of the adhesive layer 2 is not particularly limited as long as the substrate layer 1 and the barrier layer 3 can be bonded, and may be, for example, about 1 μm or more, or about 2 μm or more. Also, the thickness of the adhesive layer 2 is, for example, about 10 μm or less, or about 5 μm or less. In addition, the preferred range of the thickness of the adhesive layer 2 is about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, or about 2 to 5 μm.
[0114] [Coloring Layer]
[0115] The colored layer is a layer (not shown) provided between the substrate layer 1 and the barrier layer 3 as required. In the case of having an adhesive layer 2, a colored layer may be provided between the substrate layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. In addition, a colored layer may be provided outside the substrate layer 1. By providing a colored layer, the outer packaging material for the power storage device can be colored. A colored adhesive layer 2 and a colored layer may also be provided between the substrate layer 1 and the barrier layer 3.
[0116] The colored layer can be formed, for example, by applying ink containing a colorant to the surface of the base layer 1 or the surface of the barrier layer 3. As the colorant, a known colorant such as a pigment or a dye can be used. In addition, the colorant can be used alone or in combination of two or more.
[0117] Specific examples of the colorant contained in the colored layer include the same colorants as those exemplified in the section of [Adhesive Layer 2].
[0118] [Barrier layer 3]
[0119] In the outer packaging material for a power storage device, the barrier layer 3 is a layer that at least suppresses the intrusion of moisture.
[0120] As the barrier layer 3, for example, metal foil, vapor-deposited film, resin layer, etc. having barrier properties can be cited. As the vapor-deposited film, metal vapor-deposited film, inorganic oxide vapor-deposited film, carbon-containing inorganic oxide vapor-deposited film, etc. can be cited. As the resin layer, polyvinylidene chloride, polymers with chlorotrifluoroethylene (CTFE) as the main component, polymers with tetrafluoroethylene (TFE) as the main component, polymers with fluoroalkyl groups, and polymers with fluoroalkyl units as the main component, etc., fluororesins, ethylene-vinyl alcohol copolymers, etc. can be cited. In addition, as the barrier layer 3, resin films provided with at least one layer of these vapor-deposited films and resin layers can also be cited. The barrier layer 3 can also be provided with multiple layers. The barrier layer 3 preferably includes a layer composed of a metal material. As the metal material constituting the barrier layer 3, specifically, aluminum alloy, stainless steel, titanium steel, steel plate, etc. can be cited. When used as a metal foil, it preferably includes at least one of an aluminum alloy foil and a stainless steel foil.
[0121] Regarding aluminum alloy foil, from the viewpoint of improving the formability of the outer packaging material for storage devices, for example, a soft aluminum alloy foil composed of an annealed aluminum alloy is more preferred, and from the viewpoint of further improving the formability, an aluminum alloy foil containing iron is preferred. In the aluminum alloy foil containing iron (100% by mass), the iron content is preferably 0.1 to 9.0% by mass, and more preferably 0.5 to 2.0% by mass. By having an iron content of more than 0.1% by mass, an outer packaging material for storage devices having better formability can be obtained. By having an iron content of less than 9.0% by mass, an outer packaging material for storage devices having better flexibility can be obtained. As the soft aluminum alloy foil, for example, an aluminum alloy foil having a composition specified in JIS H4160: 1994 A8021 H-O, JIS H4160: 1994 A8079 H-O, JIS H4000: 2014 A8021 P-O, or JIS H4000: 2014 A8079 P-O can be cited. In addition, silicon, magnesium, copper, manganese, etc. can also be added as needed. In addition, softening can be performed by annealing treatment, etc.
[0122] In addition, examples of stainless steel foil include austenite, ferrite, austenite-ferrite, martensite, precipitation hardening stainless steel foil, etc. From the viewpoint of providing an outer packaging material for a power storage device with better formability, the stainless steel foil is preferably made of austenite stainless steel.
[0123] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L. Among these, SUS301 and SUS304 are particularly preferred.
[0124] Regarding the thickness of the barrier layer 3, in the case of a metal foil, as long as it functions as a barrier layer that at least inhibits the infiltration of moisture, for example, it may be about 9 to 200 μm. The thickness of the barrier layer 3 is preferably about 85 μm or less, more preferably about 50 μm or less, further preferably about 40 μm or less, and particularly preferably about 35 μm or less. Furthermore, the thickness of the barrier layer 3 is preferably about 10 μm or more, further preferably about 20 μm or more, and more preferably about 25 μm or more. In addition, as a preferred range of the thickness of the barrier layer 3, there can be listed about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is composed of an aluminum alloy foil, the above range is particularly preferred. In addition, in particular, when the barrier layer 3 is composed of a stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, further preferably about 40 μm or less, further preferably about 30 μm or less, and particularly preferably about 25 μm or less. In addition, the thickness of the stainless steel foil is preferably about 10 μm or more, more preferably about 15 μm or more. In addition, as a preferred range of the thickness of the stainless steel foil, there can be listed 10 to 60 μm, 10 to 50 μm, 10 to 40 μm, 10 to 30 μm, 10 to 25 μm, 15 to 60 μm, 15 to 50 μm, 15 to 40 μm, 15 to 30 μm, and 15 to 25 μm.
[0125] In addition, when the barrier layer 3 is a metal foil, in order to prevent dissolution or corrosion, it is preferred that at least the surface opposite to the substrate layer has a corrosion-resistant coating. The barrier layer 3 may also have a corrosion-resistant coating on both surfaces. Among them, the corrosion-resistant coating refers to, for example, a thin film obtained by subjecting the surface of the barrier layer to a hot water modification treatment such as a boehm film treatment, a chemical surface treatment, anodizing treatment, a plating treatment of nickel or chromium, or an anti-corrosion treatment by coating a coating agent so that the barrier layer has corrosion resistance. As a treatment for forming a corrosion-resistant coating, one type may be performed, or two or more types may be combined. In addition, it may not be just one layer, but may be multi-layered. Further, among these treatments, the hot water modification treatment and the anodizing treatment are treatments that use a treatment agent to dissolve the surface of the metal foil to form a metal compound with excellent corrosion resistance. In addition, these treatments are sometimes also included in the definition of chemical surface treatment. In addition, when the barrier layer 3 has a corrosion-resistant coating, the corrosion-resistant coating is included as the barrier layer 3.
[0126] The corrosion-resistant coating exhibits the following effects when forming the outer packaging material for the storage device: preventing delamination between the barrier layer (such as aluminum alloy foil) and the substrate layer; preventing the surface of the barrier layer from being dissolved and corroded by hydrogen fluoride generated by the reaction of electrolyte and water, especially when the barrier layer is an aluminum alloy foil, preventing the aluminum oxide present on the surface of the barrier layer from being dissolved and corroded; and improving the adhesion (wettability) of the barrier layer surface; preventing delamination of the substrate layer and the barrier layer during heat sealing; and preventing delamination of the substrate layer and the barrier layer during forming.
[0127] As corrosion-resistant films formed by chemical surface treatment, various films are known, and corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds and rare earth oxides can be mainly listed. As chemical surface treatment using phosphates and chromates, for example, chromic acid chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, chromate treatment, etc. can be listed, and as chromium compounds used in these treatments, for example, chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium dihydrogen phosphate, chromic acid acetoacetate, chromium chloride, potassium chromium sulfate, etc. can be listed. In addition, as phosphorus compounds used in these treatments, sodium phosphate, potassium phosphate, ammonium phosphate, polyphosphoric acid, etc. can be listed. In addition, as chromate treatment, etching chromate treatment, electrolytic chromate treatment, coating type chromate treatment, etc. can be listed, and coating type chromate treatment is preferred. The coating type chromate treatment is a treatment as follows: first, the surface of at least the inner layer side of the barrier layer (for example, aluminum alloy foil) is degreased by a known treatment method such as alkali immersion, electrolytic cleaning, acid cleaning, electrolytic acid cleaning, acid activation, etc., and then a treatment liquid containing a phosphate metal salt such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, Zn (zinc) phosphate, and a mixture of these metal salts, or a treatment liquid containing a phosphate nonmetallic salt and a mixture of these nonmetallic salts, or a treatment liquid composed of a mixture of these and a synthetic resin, etc., is applied to the degreased surface by a known coating method such as roll coating, gravure printing, dipping, etc., and then dried. The treatment liquid can be various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, ether solvents, etc., preferably water. In addition, as the resin component used at this time, polymers such as phenolic resins or acrylic resins can be listed, and chromate treatment using an amino-phenolic polymer having repeating units represented by the following general formulas (1) to (4) can be listed. In addition, in the amino-phenolic polymer, the repeating units represented by the following general formulas (1) to (4) can contain one type alone, or any combination of two or more types. The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylate copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer or their derivatives such as sodium salts, ammonium salts, amine salts, etc. Particularly preferred are derivatives of polyacrylic acid such as ammonium salts, sodium salts or amine salts of polyacrylic acid. In the present invention, polyacrylic acid refers to a polymer of acrylic acid. In addition, the acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic anhydride, and is also preferably an ammonium salt, sodium salt or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic anhydride. In addition, only one type of acrylic resin can be used, or two or more types can be mixed and used.
[0128]
[0129]
[0130] In the general formulae (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group or a benzyl group. 1 and R 2 are the same or different and represent hydroxyl, alkyl or hydroxyalkyl. 1 and R 2 The alkyl group represented by , for example, can be a linear or branched alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. 1 and R 2 The hydroxyalkyl group represented by the above-mentioned group includes, for example, a linear or branched alkyl group having 1 to 4 carbon atoms substituted with one hydroxyl group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. In the general formulas (1) to (4), X, R 1 and R 2 The alkyl group and the hydroxyalkyl group shown may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxyl group or a hydroxyalkyl group. The number average molecular weight of the aminophenolic polymer having repeating units represented by the general formulae (1) to (4) is, for example, preferably in the range of 5 to 1,000,000, and more preferably in the range of 1,000 to 20,000. The aminophenolic polymer can be produced, for example, by the following method: a phenolic compound or a naphthol compound is condensed with formaldehyde to produce a polymer composed of repeating units represented by the general formula (1) or (3), and then, using formaldehyde and an amine (R 1 R 2 NH) will be functional group (-CH2NR 1 R 2 ) is introduced into the polymer obtained above. The aminated phenolic polymer may be used alone or in combination of two or more.
[0131] As other examples of corrosion-resistant coatings, films formed by coating a coating-type anti-corrosion treatment containing at least one coating agent selected from rare earth oxide sol, anionic polymers, and cationic polymers can be cited. The coating agent can also contain phosphoric acid or phosphate, and a cross-linking agent for cross-linking the polymer. Rare earth oxide sol is a liquid dispersion medium in which particles of rare earth oxide (e.g., particles with an average particle size of less than 100 nm) are dispersed. As rare earth oxides, cerium oxide, yttrium oxide, neodymium oxide, lanthanum oxide, etc. can be cited. From the viewpoint of further improving adhesion, cerium oxide is preferred. The rare earth oxides contained in the corrosion-resistant coating can be used alone or in combination of two or more. As the liquid dispersion medium of the rare earth oxide sol, various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, ether solvents, etc. can be used, preferably water. As cationic polymers, for example, polyethyleneimine, ionic polymer complexes formed by polyethyleneimine and polymers having carboxylic acids, primary amine grafted acrylic resins formed by graft polymerization of primary amines with acrylic acid main skeletons, polyallylamine or its derivatives, amino phenolic polymers, etc. are preferred. In addition, as anionic polymers, poly(methyl)acrylic acid or its salts, or copolymers with (methyl)acrylic acid or its salts as main components are preferred. In addition, the crosslinking agent is preferably selected from at least one of a compound having any functional group among isocyanate group, glycidyl group, carboxyl group, oxazoline group and a silane coupling agent. In addition, the above-mentioned phosphoric acid or phosphate is preferably condensed phosphoric acid or condensed phosphate.
[0132] An example of a corrosion-resistant coating is a coating formed by dispersing fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, tin oxide, or barium sulfate in phosphoric acid, applying the resulting dispersion to the surface of the barrier layer, and baking the dispersion at 150° C. or higher.
[0133] If necessary, the corrosion-resistant coating may be formed into a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and the anionic polymer include the above-mentioned polymers.
[0134] Here, the composition analysis of the corrosion-resistant film can be performed using, for example, time-of-flight secondary ion mass spectrometry.
[0135] There is no particular limitation on the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical reaction surface treatment. For example, in the case of a coating-type chromate treatment, it is desirable to form a corrosion-resistant film on the surface of the barrier layer 3 by 1 m2. 2On the surface, the content of the chromic acid compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium, the content of the phosphorus compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus, and the content of the aminophenol polymer is, for example, about 1.0 to 200 mg, preferably about 5.0 to 150 mg.
[0136] There is no particular limitation on the thickness of the corrosion-resistant coating. From the perspective of the cohesive force of the coating and the adhesion to the barrier layer or the heat-fusible resin layer, a thickness of 1 nm to 20 μm is preferred, 1 nm to 100 nm is more preferred, and 1 nm to 50 nm is further preferred. The thickness of the corrosion-resistant coating can be measured by observation using a transmission electron microscope or by a combination of observation using a transmission electron microscope and energy dispersive X-ray spectroscopy or electron beam energy loss spectroscopy. By analyzing the composition of the corrosion-resistant coating using time-of-flight secondary ion mass spectrometry, secondary ions (e.g., Ce2PO4 + 、CePO4 - At least one of the above), for example, secondary ions composed of Cr, P and O (such as CrPO2 + 、CrPO4 - At least one of the above (etc.) peaks.
[0137] After applying a solution containing a compound for forming a corrosion-resistant coating to the surface of the barrier layer by rod coating, roller coating, gravure coating, dipping, etc., the temperature of the barrier layer is heated to about 70 to 200°C, thereby performing a chemical surface treatment. In addition, before the barrier layer is subjected to a chemical surface treatment, the barrier layer may be subjected to a degreasing treatment by an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, etc. In this way, the surface of the barrier layer can be more effectively subjected to a chemical surface treatment. In addition, by using an acid degreasing agent formed by dissolving a fluorine-containing compound in an inorganic acid in the degreasing treatment, not only the degreasing effect of the metal foil is achieved, but also a passive metal fluoride can be formed. In this case, only the degreasing treatment may be performed.
[0138] [Thermal Fusible Resin Layer 4]
[0139] In the packaging material for a power storage device of the present invention, the heat-fusible resin layer 4 corresponds to the innermost layer and is a layer (sealing layer) that performs the function of sealing the power storage device element by heat-fusion bonding the heat-fusible resin layers when assembling the power storage device.
[0140] The resin constituting the heat-fusible resin layer 4 is not particularly limited as long as it can be heat-fused, and is preferably a resin containing a polyolefin skeleton, such as polyolefin and acid-modified polyolefin. The fact that the resin constituting the heat-fusible resin layer 4 contains a polyolefin skeleton can be analyzed by, for example, infrared spectroscopy, gas chromatography-mass spectrometry, etc. In addition, if the resin constituting the heat-fusible resin layer 4 is analyzed by infrared spectroscopy, it is preferred to detect a peak derived from maleic anhydride. For example, if maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak at a wave number of 1760 cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the thermally fusible resin layer 4. When the thermally fusible resin layer 4 is a layer composed of maleic anhydride-modified polyolefin, if the infrared spectroscopy is used for measurement, a peak derived from maleic anhydride is detected. However, when the acid modification degree is low, the peak becomes smaller and sometimes cannot be detected. In this case, it can be analyzed by nuclear magnetic resonance spectroscopy.
[0141] As polyolefins, specifically, polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be cited; ethylene-α-olefin copolymers; polypropylenes such as homopolymer polypropylene, block copolymers of polypropylene (for example, block copolymers of propylene and ethylene), and random copolymers of polypropylene (for example, random copolymers of propylene and ethylene); propylene-α-olefin copolymers; terpolymers of ethylene-butene-propylene, etc. Among them, polypropylene is preferred. The polyolefin resin in the case of a copolymer may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0142] In addition, the polyolefin may also be a cyclic polyolefin. Cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. As the olefin constituting the above-mentioned cyclic polyolefin, for example, ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, isoprene, etc. can be cited. In addition, as the cyclic monomer constituting the cyclic polyolefin, for example, cyclic olefins such as norbornene can be cited; cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene can be cited. Among them, preferred cyclic olefins can be cited, and more preferably norbornene.
[0143] Acid-modified polyolefin refers to a polymer modified by block polymerization or graft polymerization of polyolefin with an acid component. As the acid-modified polyolefin, the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a cross-linked polyolefin can also be used. In addition, as the acid component used in the acid modification, for example, carboxylic acids or anhydrides thereof such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride can be cited.
[0144] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin refers to a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin in place of the acid component, or by block polymerization or graft polymerization of the acid component to the cyclic polyolefin. The acid-modified cyclic polyolefin is the same as described above. In addition, the acid component used in the acid modification is the same as the acid component used in the modification of the above-mentioned polyolefin.
[0145] Preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylene modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polypropylene.
[0146] The heat-adhesive resin layer 4 may be formed of one resin alone or a blended polymer of two or more resins. Furthermore, the heat-adhesive resin layer 4 may be formed of only one layer or two or more layers of the same or different resins.
[0147] In addition, the heat-fusible resin layer 4 may also contain a lubricant as needed. When the heat-fusible resin layer 4 contains a lubricant, the formability of the outer packaging material for the storage device can be improved. There is no particular limitation on the lubricant, and a known lubricant can be used. One lubricant may be used alone, or two or more lubricants may be used in combination.
[0148] The lubricant is not particularly limited, but an amide lubricant is preferred. Specific examples of the lubricant include the lubricants exemplified in the substrate layer 1. The lubricant may be used alone or in combination of two or more.
[0149] When a lubricant is present on the surface of the heat-fusible resin layer 4, the amount thereof is not particularly limited, but is preferably 10 to 50 mg / m 2 More preferably, 15 to 40 mg / m 2 degree.
[0150] The lubricant present on the surface of the thermally adhesive resin layer 4 may be a lubricant that is caused to seep out of the resin constituting the thermally adhesive resin layer 4 or a lubricant that is coated on the surface of the thermally adhesive resin layer 4 .
[0151] The thickness of the heat-fusible resin layer 4 is not particularly limited as long as the function of heat-fusible resin layers being heat-fused to each other to seal the storage device element can be fulfilled, and can be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. Among them, for example, when the thickness of the adhesive layer 5 described later is 10 μm or more, the thickness of the heat-fusible resin layer 4 can be preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 5 described later is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-fusible resin layer 4 can be preferably about 20 μm or more, and more preferably about 35 to 85 μm.
[0152] [Adhesive layer 5]
[0153] In the packaging material for a power storage device of the present invention, the adhesive layer 5 is a layer provided between the barrier layer 3 (or the corrosion-resistant coating) and the heat-fusible resin layer 4 as necessary in order to firmly adhere them.
[0154] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-fusible resin layer 4. As the resin used in forming the adhesive layer 5, for example, the same resin as the adhesive exemplified in the adhesive layer 2 can be used. In addition, from the viewpoint of firmly bonding the adhesive layer 5 and the heat-fusible resin layer 4, the resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and the polyolefins and acid-modified polyolefins exemplified in the above-mentioned heat-fusible resin layer 4 can be listed. On the other hand, from the viewpoint of firmly bonding the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 preferably contains an acid-modified polyolefin. As the acid-modified component, dicarboxylic acids such as maleic acid, itaconic acid, succinic acid, and adipic acid or their anhydrides, acrylic acid, methacrylic acid, etc. can be listed. From the viewpoint of ease of modification and versatility, maleic anhydride is most preferred. In addition, from the viewpoint of heat resistance of the outer packaging material for storage devices, it is preferred that the olefin component is a polypropylene resin, and it is most preferred that the adhesive layer 5 contains maleic anhydride-modified polypropylene.
[0155] The resin constituting the adhesive layer 5 contains a polyolefin skeleton, which can be analyzed by, for example, infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 contains an acid-modified polyolefin, for example, when measuring maleic anhydride-modified polyolefin by infrared spectroscopy, the wavelength at 1760 cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride can be detected near 1.174°. However, when the degree of acid modification is low, the peak becomes smaller and sometimes cannot be detected. In this case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0156] In addition, from the viewpoints of durability such as heat resistance and resistance to contents of the outer packaging material for a storage battery device, and reducing the thickness while ensuring formability, it is more preferable that the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the above-mentioned acid-modified polyolefins can be preferably exemplified.
[0157] In addition, the adhesive layer 5 is preferably a cured product comprising an acid-modified polyolefin and a resin composition selected from at least one of a compound with an isocyanate group, a compound with an oxazoline group and a compound with an epoxy group, and is particularly preferably a cured product comprising an acid-modified polyolefin and a resin composition selected from at least one of a compound with an isocyanate group and a compound with an epoxy group. In addition, the adhesive layer 5 preferably includes at least one selected from polyurethane, polyester and epoxy resin, and more preferably includes polyurethane and epoxy resin. As polyester, preferably, for example, an ester resin generated by the reaction of an epoxy group and a maleic anhydride group, an amide ester resin generated by the reaction of an oxazoline group and a maleic anhydride group. Wherein, in the adhesive layer 5, there is a compound with an isocyanate group, a compound with an oxazoline group, an epoxy resin and the like, and the presence of the unreacted product can be confirmed by a method selected from infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0158] In addition, from the viewpoint of further improving the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent, and the curing agent has at least one selected from an oxygen atom, a heterocyclic ring, a C=N bond, and a COC bond. As a curing agent having a heterocyclic ring, for example, a curing agent having an oxazoline group, a curing agent having an epoxy group, etc. can be cited. In addition, as a curing agent having a C=N bond, a curing agent having an oxazoline group, a curing agent having an isocyanate group, etc. can be cited. In addition, as a curing agent having a COC bond, a curing agent having an oxazoline group, a curing agent having an epoxy group, etc. can be cited. The fact that the adhesive layer 5 is a cured product of a resin composition containing these curing agents can be confirmed by methods such as gas chromatography-mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray photoelectron spectroscopy (XPS).
[0159] There are no particular restrictions on the compound having an isocyanate group. From the viewpoint of effectively improving the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably cited. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), substances obtained by polymerizing or ureating them, mixtures thereof, or copolymers with other polymers. In addition, adducts, biuret bodies, isocyanurate bodies, etc. can be cited.
[0160] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0161] As long as the compound with oxazoline group comprises the compound of oxazoline skeleton, it is not particularly limited.As the specific example of the compound with oxazoline group, the compound with polystyrene main chain, the compound with acrylic acid main chain etc. can be enumerated.In addition, as commercially available product, the EPOCROS series etc. of such as Japan Catalyst Co., Ltd. system can be enumerated.
[0162] The ratio of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0163] As a compound having an epoxy group, for example, an epoxy resin can be cited. As the epoxy resin, there is no particular limitation as long as it is a resin that can form a cross-linked structure using the epoxy group present in the molecule, and a known epoxy resin can be used. As the weight average molecular weight of the epoxy resin, preferably 50 to 2000, more preferably 100 to 1000, and further preferably 200 to 800 can be cited. Among them, in the first disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under the condition of using polystyrene as a standard sample.
[0164] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, bisphenol F type glycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. The epoxy resin may be used alone or in combination of two or more.
[0165] The proportion of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5 . This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 .
[0166] The polyurethane is not particularly limited, and known polyurethanes can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.
[0167] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50% by mass, and more preferably in the range of 0.5 to 40% by mass, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere where there are components that cause corrosion of the barrier layer, such as an electrolyte.
[0168] Among them, when the adhesive layer 5 is a cured product of a resin composition comprising at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the above-mentioned acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group function as a curing agent, respectively.
[0169] The adhesive layer 5 may contain a modifier having a carbodiimide group.
[0170] The thickness of the adhesive layer 5 is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, or about 5 μm or less. Furthermore, the thickness of the adhesive layer 5 is preferably about 0.1 μm or more, or about 0.5 μm or more. In addition, as the range of the thickness of the adhesive layer 5, preferably 0.1 to 50 μm, 0.1 to 40 μm, 0.1 to 30 μm, 0.1 to 20 μm, 0.1 to 5 μm, 0.5 to 50 μm, 0.5 to 40 μm, 0.5 to 30 μm, 0.5 to 20 μm, or 0.5 to 5 μm. More specifically, in the case of a cured product of the adhesive, acid-modified polyolefin, and curing agent exemplified in the adhesive layer 2, preferably 1 to 10 μm, more preferably 1 to 5 μm. In addition, when the resin exemplified in the heat-fusible resin layer 4 is used, the thickness is preferably about 2 to 50 μm, and more preferably about 10 to 40 μm. Among them, when the adhesive layer 5 is a cured product of a resin composition containing an adhesive exemplified in the adhesive layer 2, an acid-modified polyolefin, and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating. In addition, when the resin exemplified in the heat-fusible resin layer 4 is used, it can be formed, for example, by extrusion molding of the heat-fusible resin layer 4 and the adhesive layer 5.
[0171] [Surface coating layer 6]
[0172] The outer packaging material for a storage device of the present invention aims to improve at least one of designability, electrolyte resistance, scratch resistance, formability, etc., and may have a surface covering layer 6 on the substrate layer 1 (on the side of the substrate layer 1 opposite to the barrier layer 3) as needed. The surface covering layer 6 is a layer located on the outermost side of the outer packaging material for a storage device when the storage device is assembled using the outer packaging material for a storage device.
[0173] The surface coating layer 6 can be formed of at least one of resins such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, epoxy resin, polyamide, fluororesin, silicone resin, phenolic resin, etc., mixtures of these resins, modified products of these resins, copolymers containing these resins, copolymers containing modified products of these resins, etc. The resin is preferably a curable resin.
[0174] When the resin forming the surface coating layer 6 is a curable resin, the resin may be either a one-liquid curable resin or a two-liquid curable resin, preferably a two-liquid curable resin. Examples of the two-liquid curable resin include two-liquid curable polyurethane, two-liquid curable polyester, and two-liquid curable epoxy resin. Among them, two-liquid curable polyurethane is preferred.
[0175] As two-liquid curable polyurethane, for example, polyurethane containing a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. It can be cited that polyols such as polyester polyols, polyether polyols and acrylic polyols are preferably used as main agents, and two-component curable polyurethanes with aromatic or aliphatic polyisocyanates as curing agents can be used. In addition, as polyols, it is particularly preferred to contain more than two of polyester polyols, polyether polyols and acrylic polyols, and it is further preferred to contain more than two of the three types of polyester polyols, polyether polyols and acrylic polyols. In addition, it is preferred that polyols contain acrylic polyols. The curing agent preferably contains aromatic isocyanate compounds. In addition, as polyol compounds, polyester polyols having hydroxyl groups in the side chains are preferably used in addition to the hydroxyl groups at the ends of the repeating units. As curing agents, aliphatic, alicyclic, aromatic, and aromatic aliphatic isocyanate compounds can be cited. As isocyanate compounds, for example, hexamethylene diisocyanate (HDI), xylene diisocyanate (XDI), isophorone diisocyanate (IPDI), hydrogenated XDI (H6XDI), hydrogenated MDI (H12MDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), etc. can be cited. In addition, polyfunctional isocyanate modified bodies derived from one or more of these diisocyanates can be cited. In addition, polymers (such as trimers) can also be used as polyisocyanate compounds. These polymers can include adducts, biuret bodies, isocyanurate bodies, etc. Among them, aliphatic isocyanate compounds refer to isocyanates having aliphatic groups and not having aromatic rings, alicyclic isocyanate compounds refer to isocyanates having alicyclic hydrocarbon groups, and aromatic isocyanate compounds refer to isocyanates having aromatic rings. Since the surface coating layer 6 is formed of polyurethane, it is possible to impart excellent electrolyte resistance to the outer packaging material for an electrical storage device.
[0176] In the surface coating layer 6, at least one of the surface and the inside of the surface coating layer 6 may contain additives such as the above-mentioned lubricant or anti-blocking agent, matting agent (filler, etc. (particles, etc.)), flame retardant, antioxidant, tackifier, antistatic agent, etc. as needed, depending on the functionality that the surface coating layer 6 or its surface should have. As additives, for example, microparticles with an average particle size of 0.5nm to 5μm can be cited. The average particle size of the additive is the median diameter measured using a laser diffraction / scattering particle size distribution measuring device.
[0177] The additive may be any of an inorganic substance and an organic substance. In addition, there is no particular limitation on the shape of the additive, and examples thereof include spherical, fibrous, plate-like, amorphous, and flaky shapes.
[0178] As the specific example of additive, talc, silicon dioxide, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, aluminum oxide, carbon black, carbon nanotube, high melting point nylon, acrylic resin, cross-linked acrylic acid, cross-linked styrene, cross-linked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. can be enumerated. One kind of additive can be used alone, and two or more kinds can be used in combination. Among these additives, from the viewpoints of dispersion stability, cost, etc., preferred silicon dioxide, barium sulfate, titanium oxide can be enumerated. In addition, various surface treatments such as insulation treatment and high dispersibility treatment can also be implemented on the surface of the additive.
[0179] As described above, for example, in the case where the outer packaging material 10 for a storage device is colored (specifically, since at least one layer of the layers of the outer packaging material 10 for a storage device located closer to the substrate layer 1 side than the barrier layer 3 (for example, the substrate layer 1, the adhesive layer 2, the coloring layer, the surface covering layer 6, etc. described later) is colored, when the outer packaging material 10 for a storage device is observed from the substrate layer 1 side, a color different from that of the barrier layer 3 is discernible), whitening of the curved portion 11 and the like are easily judged as defective products, and the quality management method of the present invention is effective, especially when the appearance of the outer packaging material 10 for a storage device is a dark color such as black. In addition, for example, in the case where the outer packaging material for a storage device is matte-style, whitening of the curved portion 11 and the like are easily judged as defective products, so the quality management method of the present invention is effective. Therefore, in the outer packaging material 10 for a storage device, the surface covering layer 6 can be colored, and preferably the surface covering layer 6 contains a matte agent. Specifically, the surface covering layer 6 is composed of a resin composition containing a resin (for example, a polyurethane formed by a mixture of a polyol compound and an aromatic isocyanate compound), inorganic particles (for example, silica particles, etc.) and organic particles. When the outer packaging material 10 for the storage device is observed from the side of the surface covering layer 6, the quality management method of the present invention is effective when the appearance is a dark black color.
[0180] The method of forming the surface coating layer 6 is not particularly limited, and an example thereof includes a method of applying a resin that forms the surface coating layer 6. When an additive is added to the surface coating layer 6, the resin mixed with the additive may be applied.
[0181] The thickness of the surface coating layer 6 is not particularly limited as long as the above-mentioned function as the surface coating layer 6 is exerted, and is, for example, about 0.5 to 10 μm, preferably about 1 to 5 μm.
[0182] Method for producing outer packaging material for power storage device
[0183] There are no particular restrictions on the method for producing an outer packaging material for a storage device as long as a laminated body formed by laminating the layers possessed by the outer packaging material for a storage device of the present invention can be obtained, and examples thereof include a method comprising the steps of laminating at least a substrate layer 1, a barrier layer 3 and a thermally fusible resin layer 4 in sequence.
[0184] An example of a method for manufacturing an outer packaging material for a storage device of the present invention is as follows. First, a laminated body (hereinafter sometimes referred to as "laminated body A") is formed by laminating a substrate layer 1, an adhesive layer 2, and a barrier layer 3 in sequence. The formation of the laminated body A can be specifically performed by the following dry lamination method: the adhesive used in the formation of the adhesive layer 2 is applied to the substrate layer 1 or the barrier layer 3 whose surface has been chemically converted as required by a coating method such as a gravure coating method or a roll coating method, and after drying, the barrier layer 3 or the substrate layer 1 is laminated to cure the adhesive layer 2.
[0185] Next, the heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is laminated directly on the barrier layer 3, the heat-fusible resin layer 4 can be laminated on the barrier layer 3 of the laminate A by a method such as a heat lamination method and an extrusion lamination method. In addition, when an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4, for example, the following methods can be cited: (1) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method); (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-fusible resin layer 4 are laminated, and laminating the laminate on the barrier layer 3 of the laminate A by a heat lamination method, or a method of forming a laminate in which the adhesive layer 5 is laminated on the barrier layer 3 of the laminate A, and laminating the laminate by a heat lamination method. (1) a method of laminating the laminate A with a heat-fusible resin layer 4; (2) a method of laminating the laminate A with a heat-fusible resin layer 4; (3) a method of pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-fusible resin layer 4 previously formed into a film sheet, and bonding the laminate A and the heat-fusible resin layer 4 using the adhesive layer 5 (sandwich lamination method); (4) a method of applying a solution of an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A and then drying it, or further laminating by a sintering method, etc., and laminating the heat-fusible resin layer 4 previously formed into a film sheet on the adhesive layer 5.
[0186] When the surface covering layer 6 is provided, the surface covering layer 6 is laminated on the surface of the substrate layer 1 on the opposite side to the barrier layer 3. The surface covering layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface covering layer 6 to the surface of the substrate layer 1. The order of the steps of laminating the barrier layer 3 on the surface of the substrate layer 1 and laminating the surface covering layer 6 on the surface of the substrate layer 1 is not particularly limited. For example, after the surface covering layer 6 is formed on the surface of the substrate layer 1, the barrier layer 3 can be formed on the surface of the substrate layer 1 on the opposite side to the surface covering layer 6.
[0187] By operating as described above, a laminated body is formed which has, in sequence, a surface covering layer 6 arranged as required / a base material layer 1 / an adhesive layer 2 arranged as required / a barrier layer 3 / an adhesive layer 5 arranged as required / a hot-melt adhesive resin layer 4. In order to strengthen the adhesion between the adhesive layer 2 and the adhesive layer 5 arranged as required, further heat treatment may be performed.
[0188] In the outer packaging material for a storage device, each layer constituting the laminate may be subjected to surface activation treatment such as corona treatment, sandblasting, acid treatment, ozone treatment, etc. as needed to improve processing adaptability. For example, by subjecting the surface of the substrate layer 1 opposite to the barrier layer 3 to corona treatment, the printing adaptability of the ink on the surface of the substrate layer 1 can be improved.
[0189] Application of packaging materials for power storage devices
[0190] The outer packaging material for a storage device of the present invention can be used in a packaging body for sealing and storing storage device elements such as a positive electrode, a negative electrode, and an electrolyte. That is, a storage device element having at least a positive electrode, a negative electrode, and an electrolyte is stored in a packaging body formed by the outer packaging material for a storage device of the present invention to prepare a storage device.
[0191] Specifically, by using the outer packaging material for an electrical storage device of the present invention, an electrical storage device element having at least a positive electrode, a negative electrode, and an electrolyte is wrapped in a state where metal terminals connected to the positive electrode and the negative electrode protrude to the outside in a manner that a flange portion (an area where heat-fusible resin layers are in contact with each other) can be formed at the periphery of the electrical storage device element, and the heat-fusible resin layers of the flange portion are heat-sealed to each other to seal, thereby providing an electrical storage device using the outer packaging material for an electrical storage device. In particular, when the electrical storage device element is housed in a packaging body formed by the outer packaging material for an electrical storage device of the present invention, the packaging body is formed in a manner that the heat-fusible resin portion of the outer packaging material for an electrical storage device of the present invention becomes the inner side (the surface in contact with the electrical storage device element). The heat-fusible resin layers of two outer packaging materials for an electrical storage device can be overlapped relative to each other, and the peripheral portions of the overlapping outer packaging materials for an electrical storage device can be heat-fused to form a packaging body. Alternatively, Fig.11As shown in the example, one power storage device is folded back and overlapped with an outer packaging material, and the peripheral edge is heat-fused to form a package. Fig.11 As shown in the example, the sides other than the folded-back sides are heat-fused and sealed on three sides to form a package body, or the package body can be folded back in a manner that can form a flange and sealed on four sides. In addition, the concave portion for accommodating the storage device element in the outer packaging material for the storage device can also be formed by deep drawing or bulging. Fig.11 As in the example shown, one power storage device packaging material may be provided with a recessed portion while the other power storage device packaging material may not be provided with a recessed portion, or the other power storage device packaging material may also be provided with a recessed portion.
[0192] The outer packaging material for the storage device of the present invention can be suitable for storage devices such as batteries (including capacitors, capacitors, etc.). In addition, the outer packaging material for the storage device of the present invention can be used for any of primary batteries and secondary batteries, preferably for secondary batteries. There is no particular restriction on the type of secondary battery to which the outer packaging material for the storage device of the present invention is applied. For example, in addition to lithium ion batteries, lithium ion polymer batteries, all-solid batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver-zinc oxide storage batteries, metal-air batteries, multivalent cation batteries, capacitors, capacitors, etc. can also be cited. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be cited as suitable applicable objects of the outer packaging material for the storage device of the present invention.
[0193] (Example)
[0194] The present invention will be described in detail below with reference to Examples, but the present invention is not limited to the Examples.
[0195] <Manufacturing of packaging materials for energy storage devices>
[0196] Examples 1-6
[0197] As the substrate layer, a stretched nylon (ONy) film (thickness 15 μm) was prepared. In addition, as the barrier layer, an aluminum foil (JIS H4160: 1994 A8021 H-O (thickness 35 μm)) was prepared. Next, the barrier layer and the substrate layer were laminated by a dry lamination method using an adhesive (a two-component polyurethane adhesive containing carbon black as a colorant), and then an aging treatment was performed to produce a laminate of substrate layer / adhesive layer (black) / barrier layer. Chemical surface treatment was applied to both sides of the aluminum foil. The chemical surface treatment of the aluminum foil is performed as follows: a treatment solution composed of a phenolic resin, a chromium fluoride compound and phosphoric acid is applied to both sides of the aluminum foil by a roller coating method so that the coating amount of chromium reaches 10 mg / m 2 (dry mass) and then sintered.
[0198] Next, maleic anhydride-modified polypropylene as an adhesive layer (thickness 20 μm) and random polypropylene as a heat-fusible resin layer (thickness 15 μm) were coextruded on the barrier layer of each laminate obtained above, thereby laminating the adhesive layer / heat-fusible resin layer on the barrier layer. Then, the surface of the substrate layer of the laminate obtained was coated with a resin composition having the composition described below (the resin was a polyurethane resin formed by a mixture of a polyol compound and an isocyanate compound) to a thickness of 3 μm to form a matte-style surface covering layer, thereby obtaining a laminate (total thickness 91 μm) in which surface covering layer (3 μm) / substrate layer (thickness 15 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (20 μm) / heat-fusible resin layer (15 μm) were laminated in this order from the outside.
[0199] Next, each obtained laminate is cut into long strips of 150 mm (TD, Transverse Direction: transverse) × 90 mm (MD, Machine Direction: longitudinal). Among them, the MD of the laminate corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the laminate corresponds to the TD of the aluminum alloy foil. Next, a long strip is arranged between a forming mold (female mold) with a diameter of 54.5 mm (TD) × 31.6 mm (MD) and a corresponding forming mold (male mold) (the female mold side is the substrate layer side), and 4 cylinders (cylinder diameter φ80 mm) are used. The pressing pressure of the cylinder is set to 0.25 MPa, and cold forming is performed with a forming depth D = 3.0 mm to obtain Figure 5 , 6 The outer packaging material for an electric storage device having a black appearance and having a recessed portion 100 having a rectangular shape in plan view as shown in the schematic diagram of FIG.
[0200] The gap between the female mold and the male mold was set to 0.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Annex 1 (reference) of the surface of the female mold was 0.8 μm. The corner R of the female mold was 2.0 mm, and the ridge R was 2.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Annex 1 (reference) of the surface of the male mold was 3.2 μm. The corner R of the male mold was 2.0 mm, and the ridge R was 2.0 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B0659-1:2002 Annex 1 (reference) of the corner R and ridge R of the male mold was 1.6 μm.
[0201] Example 7
[0202] As the substrate layer, a stretched nylon (ONy) film (thickness 12 μm) was prepared. In addition, as the barrier layer, a stainless steel foil (SUS304 (thickness 20 μm)) was prepared. Next, the barrier layer and the substrate layer were laminated by a dry lamination method using an adhesive (a two-component polyurethane adhesive containing carbon black as a colorant), and then an aging treatment was performed to produce a laminate of substrate layer / adhesive layer (black) / barrier layer. Chemical surface treatment was applied to both sides of the stainless steel foil. The chemical surface treatment of the stainless steel foil is performed as follows: a treatment solution composed of a phenolic resin, a chromium fluoride compound and phosphoric acid is applied to both sides of the stainless steel foil by a roller coating method so that the coating amount of chromium reaches 10 mg / m 2 (dry mass) and then sintered.
[0203] Next, a modified olefin adhesive (the thickness of the adhesive layer after curing is 3 μm) is used to bond the barrier layer and the thermally fusible resin layer of the laminate obtained above by dry lamination, and the adhesive layer and the thermally fusible resin layer are stacked on the barrier layer. As the thermally fusible resin layer, an unstretched polypropylene film (thickness 23 μm) is used. Then, a resin composition 2 having the composition described below (the resin is a polyurethane resin formed by a mixture of a polyol compound and an isocyanate compound) is applied to the surface of the substrate layer of the laminate obtained so that the thickness reaches 3 μm to form a matte-style surface covering layer, thereby obtaining a laminate (total thickness 64 μm) in which surface covering layer (3 μm) / substrate layer (thickness 12 μm) / adhesive layer (3 μm) / barrier layer (20 μm) / adhesive layer (3 μm) / thermal fusible resin layer (23 μm) are stacked in sequence from the outside. The obtained laminate is formed in the same manner as in Examples 1 to 6 to obtain Figure 5 , 6 The outer packaging material for an electric storage device having a black appearance and having a recessed portion 100 having a rectangular shape in plan view as shown in the schematic diagram of FIG.
[0204] Example 8
[0205] When forming the surface coating layer, the same operation as in Example 7 was performed except that the following resin composition 3 was used instead of the resin composition 2 to form the surface coating layer, and the Figure 5 , 6 The outer packaging material for an electric storage device having a black appearance and having a recessed portion 100 having a rectangular shape in plan view as shown in the schematic diagram of FIG.
[0206] [Resin composition of surface coating layer]
[0207] In the examples, resin compositions having the following compositions were used to form the surface covering layers.
[0208] (Resin composition 1 (used in Example 1))
[0209] A resin composition containing a resin (polyurethane formed from a mixture of a polyol compound and an aliphatic isocyanate compound), inorganic particles (barium sulfate particles with an average particle size of 1 μm), organic particles (average particle size of 2 μm) and olefin wax.
[0210] (Resin composition 2 (used in Examples 2 and 7))
[0211] A resin composition containing a resin (polyurethane formed from a mixture of two polyol compounds and an aliphatic isocyanate compound), inorganic particles (silicon dioxide particles with an average particle size of 1 μm), organic particles (average particle size of 2 μm) and an olefin wax.
[0212] (Resin composition 3 (used in Examples 3 and 8))
[0213] A resin composition containing a resin (a polyurethane formed by a mixture of two polyol compounds and an aromatic isocyanate compound (the mixing ratio of the two polyol compounds is different from that of the resin composition 2)), inorganic particles (silicon dioxide particles with an average particle size of 1 μm) and organic particles (average particle size of 2 μm).
[0214] (Resin composition 4 (used in Example 4))
[0215] The content of inorganic particles in the resin composition of Example 2 was reduced.
[0216] (Resin composition 5 (used in Example 5))
[0217] The content of inorganic particles in the resin composition of Example 3 was reduced.
[0218] (Resin composition 6 (used in Example 6))
[0219] A resin composition containing a resin (a polyurethane formed by a mixture of two polyol compounds and an aromatic isocyanate compound (the mixing ratio of the two polyol compounds is different from that of the resin composition of Example 3)), inorganic particles (silicon dioxide particles with an average particle size of 1 μm), organic particles (average particle size of 2 μm) and olefin wax.
[0220] <Judgment process>
[0221] The curved portion of the outer surface of each storage device packaging material obtained in the examples on the substrate layer side where the recess is formed, i.e., the corner portion ( Figure 5 , 6 The curved portion 11 shown in the schematic diagram of the concave portion, and the non-curved portion ( Figure 5, 6 The non-curved surface portion 12 (the central portion of the concave portion 100) shown in the schematic diagram of FIG. 1 is measured under the following conditions: * a * b * L in color space * Value, a * Value and b * The observation conditions of the Konica Minolta spectrophotometer (CM-700d) calibrated with a white calibration plate (CM-A177: Konica Minolta) were set to 10°, the observation light source was set to F2, and the SCI mode (JIS Z8722-2009) was set. Next, the L values of the outer surface (substrate layer side) of the curved surface and the non-curved surface were measured at room temperature and humidity. * Value, a * Value, b * The measurement diameter was set to 8 mmφ for the curved surface and 3 mmφ for the non-curved surface. * The value of ab is based on the formula ΔE * ab=[(ΔL) 2 +(Δa) 2 +(Δb) 2 ] 1 / 2 The results are shown in Table 1. In Table 1, L * The value is the value after rounding off the second decimal place of the measured value. * Value and b * The values are respectively the values after rounding off the third decimal place of the measured values. The determination process was performed to confirm the L values of the curved surface and the non-curved surface in Examples 1 to 5, 7, and 8. * The absolute value of the difference between the values is 1.5 or less, and in Example 6, the absolute value of the difference exceeds 1.5.
[0222] <Observation using a scanning electron microscope>
[0223] Next, for the L measured in the above <Judgment Step> * Value, a * Value and b * The curved surface of the value was observed with a scanning electron microscope (magnification 1,000 times). The obtained images are shown in Figure 7 (Example 1), Figure 8 (Example 2), Fig. 9 (Example 3), Fig.10 (Example 6). As a result, in L *In the packaging materials for power storage devices of Examples 1 to 5, where the absolute value of the difference between the values is less than 1.5, no cracks occur on the curved surface and they can be judged as qualified products. In the packaging materials for power storage devices of Examples 7 and 8, no cracks occur on the curved surface and they can be judged as qualified products. * In the packaging material for a storage device of Example 6, in which the absolute value of the difference between the values exceeds 1.5, very fine cracks are generated in the curved surface portion, and the packaging material is judged as a defective product in the above judgment step. * The absolute value of the difference between the values being 1.5 or less is an example of a criterion, and this criterion may not be used in the quality management method and the method for manufacturing a power storage device of the present invention. The cracks observed by a scanning electron microscope were evaluated according to the following criteria, and the results are shown in Table 1.
[0224] A: No cracks were generated.
[0225] B: Cracks occurred, but each crack was small and the number of cracks was small.
[0226] C: Cracks occurred, each crack was large, and the number of cracks was very large.
[0227] <Appearance Evaluation>
[0228] In the above-mentioned <Judgment Step>, L * Value, a * Value and b * The curved surface and the non-curved surface of the value were visually observed by a skilled person in evaluating the whitening of the formed packaging material for a storage device, and the appearance was evaluated according to the following criteria. The results are shown in Table 1.
[0229] A: The curved and non-curved face parts have the same appearance.
[0230] B: It can be seen that the curved surface portion is slightly whitened compared to the non-curved surface portion, but the whitening is to such an extent that even an experienced person cannot easily judge.
[0231] C: It can be seen that the curved surface portion is slightly whitened compared to the non-curved surface portion, but the whitening is to such an extent that it is difficult for an unskilled person to detect.
[0232] <Measurement of specular gloss>
[0233] The mirror gloss of the outer surface of the surface covering layer of each outer packaging material for storage devices before forming was measured by the following measurement method. According to the method specified in JIS Z 8741 (1997), the mirror gloss of the surface covering layer at an incident angle of 60 degrees was measured using a gloss measuring instrument micro-tri-gloss (measurement area 9mm×15mm) manufactured by Toyo Seiki Seisaku-sho. The results are shown in Table 1. The mirror gloss recorded in Table 1 is the value after rounding off to the second decimal place of the measured value.
[0234] [Table 1]
[0235]
[0236] According to the results of Examples 1 to 8, by applying the quality control method of the present invention to the molding process of the packaging material for a storage device, it is possible to obtain the L values of the curved surface portion and the non-curved surface portion forming the concave portion. * The value is used to determine whether the outer packaging material for the storage device with the recessed portion is a qualified product. Such a quality management method is a new quality management method, and compared with the existing quality management using visual inspection or a camera, it is possible to perform quality management with higher precision. Therefore, by using the quality management method of the present invention when manufacturing storage devices, qualified storage devices can be efficiently manufactured. Among them, in the observation using a scanning electron microscope, the product with a crack evaluation of B has small cracks and a small number on the curved surface, so the cracks are discontinuous, and the surface covering layer exists in the form of a film. The product with a crack evaluation of C has large cracks and a large number, so the cracks on the curved surface are continuous, and the surface covering layer exists in the form of an island, which is in a state that is easy to peel off.
[0237] <Evaluation of electrolyte resistance>
[0238] The L * Value, a * Value and b * The non-bending part and the curved part of the value were respectively dripped with 3 drops of electrolyte (1 mol / L lithium hexafluorophosphate solution, ethylene carbonate: diethyl carbonate: dimethyl carbonate = 1:1:1 (volume ratio) solvent). After 20 minutes, the dripped electrolyte was wiped off with a rag impregnated with isopropyl alcohol (IPA). Next, the curved part was visually observed and the electrolyte resistance was evaluated according to the following criteria. The results are shown in Table 2.
[0239] A: No peeling of the surface coating layer was observed.
[0240] C: Peeling of the surface covering layer was observed.
[0241] [Table 2]
[0242]
[0243] The outer packaging materials for storage devices prepared in Examples 1 to 8 are matte in style with the surface coating layer containing inorganic particles, so it can be said that they are outer packaging materials for storage devices that are prone to fine cracks due to molding. Despite such outer packaging materials for storage devices, according to the comparison of the evaluation of electrolyte resistance of Examples 3, 5, 7, and 8 with that of Example 6, it can be seen that the L * The value is the same as the L of the non-curved surface 12 * In Examples 3, 5, 7, and 8 in which the absolute value of the difference between the values was managed to be 1.5 or less, the electrolyte resistance was particularly excellent.
[0244] As described above, the present invention provides the following aspects of the invention.
[0245] Item 1. A quality management method in a molding process of an outer packaging material for a storage device,
[0246] The quality management method takes an outer packaging material for an electric storage device as an object of quality management, the outer packaging material for an electric storage device is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside, the outer packaging material for an electric storage device is formed in a manner protruding from the heat-fusible resin layer side to the base layer side, and a recessed portion capable of accommodating an electric storage device element is formed on the heat-fusible resin layer side.
[0247] The quality control method includes a determination step in which an outer packaging material for a storage device to be inspected is extracted from an outer packaging material for a storage device having the recess formed therein, and the L values of reflected light are measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for the storage device to be inspected, respectively, under the measurement conditions of an SCI method, a field of view of 10°, and a light source of F2. * a * b * L in color space * Value, based on L * The magnitude of the difference between the two values is used to determine whether the outer packaging material for a storage battery device having the recessed portion is a qualified product.
[0248] Item 2. The quality control method according to Item 1, wherein in the judgment step, the L of the curved surface portion is * The value is the same as the L of the non-curved surface * Products whose absolute value of the difference between the values was 1.5 or less were judged to be acceptable.
[0249] Item 3. The quality management method according to Item 1 or 2, wherein the power storage device packaging material has a surface covering layer on the outside of the base layer.
[0250] Item 4. The quality management method according to any one of Items 1 to 3, wherein the outer packaging material for an electric storage device has an adhesive layer between the base layer and the barrier layer.
[0251] The adhesive layer is colored.
[0252] Item 5. A method for manufacturing an electric storage device, the electric storage device being formed by sealing an electric storage device element with a packaging body, the packaging body being formed by heat-melting the heat-melting resin layer at the periphery of an outer packaging material for an electric storage device composed of a laminate having at least a base layer, a barrier layer and a heat-melting resin layer in this order from the outside, the method for manufacturing the electric storage device comprising:
[0253] a step of preparing an outer packaging material for an electric storage device, the outer packaging material for an electric storage device having a recessed portion for housing an electric storage device element so as to protrude from the heat-fusible resin layer side of the outer packaging material for an electric storage device toward the base material layer side;
[0254] In a judgment step, a storage device outer packaging material to be inspected is extracted from the storage device outer packaging material having the above-mentioned recess formed therein, and L of reflected light is measured for the curved portion and the non-curved portion of the outer surface of the storage device outer packaging material to be inspected, respectively, under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b * L in color space * Value, based on L * The difference between the values is determined by judging whether the outer packaging material for the power storage device having the recessed portion is a qualified product; and
[0255] The process of manufacturing the electric storage device by accommodating the electric storage device element in the concave portion of the electric storage device outer packaging material,
[0256] When the formed electricity storage device packaging material is determined to be a good product as a result of the determination step, it is determined that the recess is properly formed, and an electricity storage device element is housed in the recess to manufacture the electricity storage device.
[0257] Item 6. The method for manufacturing an electric storage device according to Item 5, wherein in the judgment step, the L of the curved surface portion is * The value is the same as the L of the non-curved surface * Products whose absolute value of the difference between the values was 1.5 or less were judged to be acceptable.
[0258] Item 7. The method for producing an electric storage device according to Item 5 or 6, wherein the electric storage device packaging material has a surface covering layer on the outside of the base layer.
[0259] Item 8. The method for producing an electric storage device according to any one of Items 5 to 7, wherein the outer packaging material for an electric storage device has an adhesive layer between the base layer and the barrier layer.
[0260] The adhesive layer is colored.
[0261] Item 9. A method for inspecting an outer packaging material for an electric storage device having a recessed portion formed therein,
[0262] The inspection method uses an outer packaging material for a storage device as an inspection object, the outer packaging material for a storage device is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside, the outer packaging material for a storage device is formed in a manner protruding from the heat-fusible resin layer side to the base layer side, and a recessed portion capable of accommodating a storage device element is formed on the heat-fusible resin layer side.
[0263] The inspection method includes a determination step in which the L of reflected light is measured for the curved portion and the non-curved portion of the outer surface of the outer packaging material for a storage device having the recess formed therein under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2. * a * b * L in color space * Value, based on L * The magnitude of the difference between the two values is used to determine whether the outer packaging material for a storage battery device having the recessed portion is a qualified product.
[0264] Item 10. The inspection method according to Item 9, wherein in the judgment step, the L of the curved surface portion is * The value is the same as the L of the non-curved surface * Products whose absolute value of the difference between the values was 1.5 or less were judged to be acceptable.
[0265] Item 11. The inspection method according to Item 9 or 10, wherein the electricity storage device packaging material has a surface covering layer on the outside of the base material layer.
[0266] Item 12. An outer packaging material for an electric storage device, comprising a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in this order from the outside,
[0267] The outer packaging material for the power storage device is formed so as to protrude from the heat-fusible resin layer side toward the base layer side, and has a recessed portion capable of accommodating a power storage device element on the heat-fusible resin layer side.
[0268] The L values of the reflected light were measured for the curved portion and the non-curved portion of the outer surface of the storage device packaging material forming the recess under the SCI method, the field of view 10°, and the light source F2. * a * b * L in color space * When the value is * The value is the same as the L of the non-curved surface * The absolute value of the difference is less than 1.5.
[0269] Item 13. The packaging material for an electric storage device according to Item 12, wherein the packaging material for an electric storage device has a surface covering layer on the outside of the base material layer.
[0270] Item 14. The outer packaging material for an electrical storage device according to Item 12 or 13, wherein the outer packaging material for an electrical storage device comprises an adhesive layer between the base layer and the barrier layer.
[0271] The adhesive layer is colored.
[0272] Item 15. An outer packaging material for an electric storage device, comprising a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in this order from the outside,
[0273] The packaging material for the storage device was formed under the following molding conditions in a manner that the packaging material protruded from the heat-fusible resin layer side to the base material layer side, a recessed portion capable of accommodating the storage device element was formed on the heat-fusible resin layer side, and the L of the reflected light was measured for the curved portion and the non-curved portion of the outer surface of the storage device packaging material forming the recess under the SCI method, the field of view 10°, and the light source F2. * a * b * L in color space * When the value is * The value is the same as the L of the non-curved surface * The absolute value of the difference is less than 1.5.
[0274] (forming conditions)
[0275] The outer packaging material for the storage device is arranged between a forming die (female die) having a diameter of 54.5 mm (TD) × 31.6 mm (MD) and a corresponding forming die (male die) in such a way that the female die side is located on the substrate layer side, and the pressing pressure (surface pressure) is set to 0.25 MPa, and cold forming is performed with a forming depth of 3.0 mm to form a concave portion in a rectangular shape when viewed from above. The gap between the female die and the male die is set to 0.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the surface roughness standard sheet for comparison in JIS B 0659-1:2002 Annex 1 (reference) of the surface of the female die is 0.8 μm. The corner R of the female die is 2.0 mm, and the ridge R is 2.5 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the surface roughness standard sheet for comparison in JIS B 0659-1:2002 Annex 1 (reference) of the surface of the male die is 3.2 μm. The corner R of the male mold was 2.0 mm, and the ridge R was 2.0 mm. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Annex 1 (reference) of the male mold corner R and ridge R was 1.6 μm.
[0276] Item 16. The packaging material for an electric storage device according to Item 15, wherein the packaging material for an electric storage device has a surface covering layer on the outside of the base layer.
[0277] Item 17. The outer packaging material for an electrical storage device according to Item 15 or 16, wherein the outer packaging material for an electrical storage device has an adhesive layer between the base layer and the barrier layer.
[0278] The adhesive layer is colored.
[0279] Item 18. An electricity storage device, wherein an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte is housed in a packaging body formed of the electricity storage device packaging material according to any one of Items 12 to 14.
[0280] Description of Reference Numerals
[0281] 1. Substrate layer
[0282] 2 Adhesive layer
[0283] 3 Barrier layer
[0284] 4 Thermally fusible resin layer
[0285] 5 Adhesive layer
[0286] 6 Surface covering
[0287] 10 Outer packaging materials for power storage devices
[0288] 11 Curved face
[0289] 11a Corner
[0290] 11b Ikeinebe
[0291] 12 Non-curved part
[0292] 13 Curved part
[0293] 14 Zhou Hongbu
[0294] 100 recesses.
Claims
1. An outer packaging material for an electric storage device, characterized in that: The invention is composed of a laminated body having at least a surface covering layer, a base material layer, a barrier layer and a heat-fusible resin layer in this order from the outside, The outer packaging material for an electric storage device is formed so as to protrude from the thermally fusible resin layer side toward the base layer side, and has a recessed portion capable of accommodating an electric storage device element on the thermally fusible resin layer side. The L values of reflected light were measured for the curved portion and the non-curved portion of the outer surface of the recessed portion of the packaging material for a storage battery device under the measurement conditions of the SCI method, a viewing field of 10°, and a light source of F2. * a * b * L in color space * When the value is * The value is related to the L of the non-curved surface * The absolute value of the difference is less than 1.
0.
2. The outer packaging material for an electric storage device according to claim 1, wherein: The surface covering layer is formed of a two-component curable polyurethane containing a polyol and a polyisocyanate.
3. The outer packaging material for an electric storage device according to claim 2, wherein: The polyisocyanate is an aromatic polyisocyanate, The aromatic polyisocyanate is xylylene diisocyanate (XDI).
4. The outer packaging material for an electric storage device according to claim 1, wherein: The surface covering layer comprises silicon dioxide.
5. The outer packaging material for an electric storage device according to claim 1, wherein: The surface covering layer comprises kaolin.
6. The outer packaging material for an electric storage device according to claim 1, wherein: The surface covering layer includes titanium oxide.
7. The outer packaging material for an electric storage device according to claim 1, wherein: The surface covering layer comprises barium sulfate.
8. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The thickness of the barrier layer is more than 50 μm and less than 85 μm.
9. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The thickness of the barrier layer is more than 10 μm and less than 50 μm.
10. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The thickness of the barrier layer is more than 85 μm and less than 200 μm.
11. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The surface covering is colored.
12. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The substrate layer is colored.
13. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: A colored layer is further provided between the substrate layer and the barrier layer.
14. The outer packaging material for an electric storage device according to claim 1 or 2, characterized in that: The barrier layer is composed of stainless steel.
15. The outer packaging material for an electric storage device according to claim 14, wherein: The stainless steel is SUS304.
16. An outer packaging material for an electric storage device, characterized in that: The invention is composed of a laminated body having at least a surface covering layer, a base material layer, a barrier layer and a heat-fusible resin layer in this order from the outside, The packaging material for a storage device is formed under the following molding conditions so as to protrude from the heat-fusible resin layer side to the base material layer side, a recessed portion capable of accommodating a storage device element is formed on the heat-fusible resin layer side, and the L of reflected light is measured under the measurement conditions of the SCI method, the field of view of 10°, and the light source F2 for the curved portion and the non-curved portion of the outer surface of the storage device packaging material forming the recessed portion. * a * b * L in color space * When the value is * The value is related to the L of the non-curved surface * The absolute value of the difference is less than 1.
0. Among them, the forming conditions are as follows: The outer packaging material for the storage device is arranged between a forming die (female die) having a diameter of 54.5 mm (TD) × 31.6 mm (MD) and a corresponding forming die (male die) in such a manner that the female die side is located on the substrate layer side, and the pressing pressure (surface pressure) is set to 0.25 MPa, and cold forming is performed with a forming depth of 3.0 mm to form a concave portion in a plan view rectangular shape; the gap between the female die and the male die is set to 0.5 mm; the maximum height roughness (nominal value of Rz) specified in Table 2 of the surface roughness standard sheet for comparison of JIS B 0659-1:2002 Annex 1 (reference) of the surface of the female die is 0.8 μm; the corner R of the female die is 2.0 mm, and the ridge R is 2.5 mm; the surface of the male die has a JIS B The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Appendix 1 (Reference) is 3.2μm; the corner R of the male mold is 2.0mm and the ridge R is 2.0mm; the maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet of JIS B 0659-1:2002 Appendix 1 (Reference) is 1.6μm.
17. The outer packaging material for an electric storage device according to claim 16, wherein: The packaging material for a power storage device comprises an adhesive layer between the base layer and the barrier layer. The adhesive layer is colored.
18. An electric storage device, characterized in that: An electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a package formed of the electricity storage device packaging material according to any one of claims 1 to 17.
Citation Information
Patent Citations
Layered package material, outer package material for battery, and the battery
JP2008287971A